Laminate, metal-clad laminate, circuit board, electronic element, device, adhesive resin composition, method for producing same, and adhesive
A laminated structure with a polyimide resin and metal salt filler in the adhesive layer addresses high transmission loss and wrinkle issues in FPCs, enhancing dielectric properties and flame retardancy for high-frequency signal transmission.
Patent Information
- Application Number
- CN202410819065.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-24
- Publication Date
- 2024-12-31
AI Technical Summary
Existing flexible printed circuits (FPCs) face challenges with high transmission loss, signal delay, uneven thickness, and wrinkle generation due to adhesive layer fluidity and tensile elastic coefficient during lamination, which compromise dielectric properties and flame retardancy.
A laminated structure with a thick adhesive layer containing a polyimide resin and a high concentration of metal salt of organic phosphinic acid filler, controlled tensile and storage elastic coefficients, and specific thickness ratios to suppress uneven thickness and wrinkles, while maintaining excellent dielectric properties and flame retardancy.
The laminated structure achieves reduced transmission loss, improved reliability, and enhanced safety for high-frequency signal transmission by controlling adhesive layer properties and filler concentration, ensuring both dielectric performance and flame retardancy.
Smart Images

Figure CN119217819A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate, a metal-clad laminate, a circuit board, an electronic element, and an electronic device that are effectively used as an electronic component material, as well as an adhesive resin composition, a method for producing the same, and an adhesive film. Background Art
[0002] In recent years, with the progress of miniaturization, lightness and space saving of electronic devices, the demand for flexible printed circuits (FPCs) that are thin, light, flexible and have excellent durability even when bent repeatedly has increased. FPCs can be installed three-dimensionally and at high density even in a limited space, so their use is gradually expanding in parts such as wiring, cables, connectors, etc. of electronic devices such as hard disk drives (HDDs), digital versatile disks (DVDs), and smartphones.
[0003] In addition to high density, the high performance of equipment has been promoted, so it is also necessary to cope with the high frequency of transmission signals. When transmitting high-frequency signals, if the transmission loss in the transmission path is large, undesirable conditions such as loss of electrical signals or prolonged signal delay time will occur. In order to cope with the high frequency of transmission signals, it is proposed to improve the dielectric properties in the following way: an adhesive layer with a large thickness ratio is placed between a pair of insulating resin layers of a single-sided metal-clad laminate, and a thermoplastic polyimide made of dimer acid-type diamine (DDA) in which the two terminal carboxylic acid groups of dimer acid are substituted with primary aminomethyl or amino groups is used as the material of the adhesive layer (Patent Document 1). In a layer structure such as Patent Document 1, in order to further improve the dielectric properties, it is effective to increase the thickness of the inner layer portion containing the adhesive layer with excellent dielectric properties and increase the thickness ratio relative to the entire resin layer.
[0004] However, if the thickness of the inner layer portion containing aliphatic groups with low polarity is increased and the thickness ratio relative to the entire resin layer is increased, the flame retardancy is impaired, which becomes an obstacle to further improving the dielectric properties.
[0005] In addition, if the thickness of the inner layer portion is increased, uneven thickness is likely to occur during coating, and if the uneven thickness is large, the characteristic impedance will vary greatly, thereby causing adverse effects such as increased loss of transmission signals.
[0006] Furthermore, when a long adhesive film and a single-sided metal-clad laminate are laminated in a roll-to-roll manner, the adhesive film is too soft and thus wrinkles are easily generated due to shear stress during lamination.
[0007] [Prior art literature]
[0008] [Patent Document]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 2018-170417 Summary of the invention
[0010] [Problems to be solved by the invention]
[0011] An object of the present invention is to provide a laminate having excellent dielectric properties and flame retardancy that can be used in a circuit board for high frequencies and can suppress the occurrence of uneven thickness of an adhesive layer or wrinkles during lamination.
[0012] [Technical means to solve the problem]
[0013] The inventors have made great efforts to study and found that the factors causing uneven thickness of the adhesive layer and wrinkles during lamination are the fluidity of the adhesive varnish or the tensile elastic coefficient of the adhesive film and the storage elastic coefficient near the lamination temperature. It was also found that by providing an adhesive layer with a large thickness and a low dielectric loss tangent in the inner layer and mixing a filler component in a high concentration in the adhesive layer, the uneven thickness and wrinkles during lamination can be improved, and the dielectric loss tangent can be reduced while ensuring excellent flame retardancy, thereby completing the present invention.
[0014] That is, the laminated body according to the first aspect of the present invention is a laminated body including: a first insulating resin layer; a second insulating resin layer; and an adhesive layer laminated between these layers so as to abut against the first insulating resin layer and the second insulating resin layer.
[0015] In the laminate of the first aspect of the present invention, the total thickness T1 of the first insulating resin layer, the adhesive layer and the second insulating resin layer is in the range of 70μm to 500μm, the thickness T2 of the adhesive layer is in the range of greater than 50μm and less than 450μm, and the ratio of T2 to T1 (T2 / T1) is in the range of greater than 0.5 and less than 0.96.
[0016] Furthermore, in the laminate according to the first aspect of the present invention, the adhesive layer contains a resin component and a filler component.
[0017] The resin component contains a polyimide having a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition based on all diamine residues, wherein the dimer diamine composition mainly contains a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group.
[0018] In the laminate according to the first aspect of the present invention, the filler component includes a metal salt of an organic phosphinic acid, and a weight ratio of the filler component relative to 100 parts by weight of the total amount of the resin component is in a range of more than 40 parts by weight and not more than 90 parts by weight.
[0019] The first aspect of the present invention may be a laminate in which, within a surface field of 100 μm × 100 μm when a thickness-direction cross-section of the bonding layer is observed under a scanning electron microscope, the total area ratio of filler components with a particle diameter exceeding 10 μm and filler detachment portions with a long diameter exceeding 10 μm is less than 1% as an average value of the surface field of view at any ten locations.
[0020] In the laminate according to the first aspect of the present invention, the polyimide may be a polyimide having a ketone group in a molecule, and the resin component may contain a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the ketone group.
[0021] In the laminate according to the first aspect of the present invention, the polyimide may form a crosslinked structure by a reaction between the polyimide having a keto group in the molecule and a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the keto group.
[0022] In the laminate according to the first aspect of the present invention, the tensile elastic coefficient of the adhesive layer may be within a range of 1.0 GPa to 1.2 GPa.
[0023] In the laminate according to the first aspect of the present invention, the adhesive layer may have a storage elastic modulus at 80° C. in the range of 10 MPa to 20 MPa.
[0024] In the laminate according to the first aspect of the present invention, the first insulating resin layer and the second insulating resin layer may be multilayer polyimide layers including a non-thermoplastic polyimide layer and a thermoplastic polyimide layer. In this case, the outermost layer of the multilayer polyimide layer may be a thermoplastic polyimide layer.
[0025] The laminated body according to the first aspect of the present invention may have a length in the width direction (transverse direction (TD) direction) within a range of 0.2 m to 2.0 m, and may be in an elongated shape.
[0026] A metal-clad laminate according to a second aspect of the present invention comprises: the laminate according to the first aspect; and a metal layer laminated on one surface or both surfaces of the laminate.
[0027] A circuit board according to a third aspect of the present invention comprises: the laminate according to the first aspect; and a wiring layer laminated on one surface or both surfaces of the laminate.
[0028] An electronic component according to a fourth aspect of the present invention includes the circuit substrate according to the third aspect.
[0029] An electronic device according to a fifth aspect of the present invention includes the circuit substrate according to the third aspect.
[0030] The adhesive resin composition according to the sixth aspect of the present invention is an adhesive resin composition containing a resin component, a filler component, and an organic solvent.
[0031] In the adhesive resin composition according to the sixth aspect of the present invention, the resin component contains a polyimide having a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition based on all diamine residues, wherein the dimer diamine composition contains as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group.
[0032] In the adhesive resin composition according to the sixth aspect of the present invention, the filler component contains a metal salt of an organic phosphinic acid, and the weight ratio of the filler component relative to 100 parts by weight of the total amount of the resin component is within a range of more than 40 parts by weight and not more than 90 parts by weight.
[0033] In the adhesive resin composition according to the sixth aspect of the present invention, the tensile elastic modulus when formed into a film with a thickness in the range of more than 50 μm and 450 μm is in the range of 1.0 GPa to 1.2 GPa, and the storage elastic modulus at 80° C. is in the range of 10 MPa to 20 MPa.
[0034] A method for producing an adhesive resin composition according to a seventh aspect of the present invention is a method for producing the adhesive resin composition according to the sixth aspect.
[0035] A method for producing an adhesive resin composition according to a seventh aspect of the present invention comprises the following steps (i) and (ii);
[0036] (i) a step of obtaining a filler dispersion by mixing a part of the resin component and the filler component in an organic solvent and stirring the mixture; and
[0037] (ii) a step of obtaining the adhesive resin composition by mixing the rest of the resin component together with an organic solvent into the filler dispersion and stirring the mixture.
[0038] In addition, in the method for producing an adhesive resin composition according to the seventh aspect of the present invention, in step (i), the weight ratio of the resin component in the filler dispersion is set to within the range of 3 parts by weight to 15 parts by weight relative to 100 parts by weight of the final total amount of the resin component, and the solid content concentration in the filler dispersion is adjusted to within the range of 40% by weight to 60% by weight, and in step (ii), the weight ratio of the filler component in the adhesive resin composition is within the range of more than 40 parts by weight and less than 90 parts by weight relative to 100 parts by weight of the final total amount of the resin component.
[0039] An adhesive film according to an eighth aspect of the present invention is an adhesive film containing a resin component and a filler component.
[0040] In the adhesive film according to the eighth aspect of the present invention, the resin component contains a polyimide having a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition based on all diamine residues, wherein the dimer diamine composition contains as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group.
[0041] In the adhesive film according to the eighth aspect of the present invention, the filler component contains a metal salt of an organic phosphinic acid, and the weight ratio of the filler component to 100 parts by weight of the total amount of the resin component is in a range of more than 40 parts by weight and not more than 90 parts by weight.
[0042] In the adhesive film according to the eighth aspect of the present invention, the thickness is more than 50 μm and less than 450 μm, the tensile elastic modulus is 1.0 GPa to 1.2 GPa, and the storage elastic modulus at 80° C. is 10 MPa to 20 MPa.
[0043] [Effects of the Invention]
[0044] The laminate of the present invention has a thick adhesive layer with a low dielectric loss tangent in the inner layer, and a filler component is mixed in a high concentration in the adhesive layer, thereby appropriately controlling the tensile elastic coefficient and the storage elastic coefficient, thereby suppressing the generation of uneven thickness and wrinkles during lamination, and achieving both excellent dielectric properties and flame retardancy. Therefore, the metal-clad laminate using the laminate of the present invention can achieve a reduction in transmission loss and an improvement in reliability and safety in the application of, for example, a circuit substrate that transmits high-frequency signals of 10 GHz or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a schematic cross-sectional view showing the layer structure of a laminated body according to a preferred embodiment of the present invention.
[0046] Figure 2 This is a schematic cross-sectional view showing the layer structure of a laminate according to another preferred embodiment of the present invention.
[0047] Figure 3 This is a schematic cross-sectional view showing the layer structure of a metal-clad laminate according to a preferred embodiment of the present invention.
[0048] Figure 4 This is a schematic cross-sectional view showing the layer structure of a metal-clad laminate according to another preferred embodiment of the present invention.
[0049] Figure 5 This is a scanning electron microscope image of a cross section of the bonding layer obtained in Example 5.
[0050] Figure 6 This is a scanning electron microscope image of a cross section of the bonding layer obtained in Comparative Example 5.
[0051] [Explanation of Symbols]
[0052] 10A, 10B: Thermoplastic polyimide layer
[0053] 20A, 20B: Non-thermoplastic polyimide layer
[0054] 30A, 30B: Thermoplastic polyimide layer
[0055] 40A: First insulating resin layer
[0056] 40B: Second insulating resin layer
[0057] 100, 101: Laminated body
[0058] 110A, 110B: Metal layer
[0059] 200, 201: Metal-clad laminate
[0060] AD: Adhesive layer DETAILED DESCRIPTION
[0061] The embodiments of the present invention will be described with reference to the drawings as appropriate.
[0062] [Laminated body]
[0063] In a laminated body of one embodiment of the present invention, a first insulating resin layer, an adhesive layer, and a second insulating resin layer are laminated in sequence. By making an adhesive layer with a low dielectric loss tangent interposed between two insulating resin layers and thickening the film, a laminated body (laminated resin film) with a low dielectric loss tangent and a large thickness is obtained. In addition, by sandwiching an insulating resin layer with a small dimensional change with an adhesive layer with a large dimensional change, dimensional stability can be ensured. Furthermore, by sandwiching an adhesive layer between two insulating resin layers, moisture absorption and water absorption of the adhesive layer can be suppressed, and degradation of the dielectric loss tangent can be alleviated.
[0064] Figure 1 The cross-sectional structure of the laminate 100 according to a preferred embodiment of the present invention is shown. The laminate 100 has a layer structure in which thermoplastic polyimide layer 10A / non-thermoplastic polyimide layer 20A / thermoplastic polyimide layer 30A / adhesive layer AD / thermoplastic polyimide layer 30B / non-thermoplastic polyimide layer 20B / thermoplastic polyimide layer 10B are laminated in this order.
[0065] Here, the thermoplastic polyimide layer 10A, the non-thermoplastic polyimide layer 20A, and the thermoplastic polyimide layer 30A constitute the first insulating resin layer 40A, and the thermoplastic polyimide layer 10B, the non-thermoplastic polyimide layer 20B, and the thermoplastic polyimide layer 30B constitute the second insulating resin layer 40B. Therefore, the laminate 100 has a structure in which the first insulating resin layer 40A, the adhesive layer AD, and the second insulating resin layer 40B are laminated in this order.
[0066] Figure 2 The cross-sectional structure of a laminate 101 according to another preferred embodiment of the present invention is shown. The laminate 101 has a layer structure in which a thermoplastic polyimide layer 10A / a non-thermoplastic polyimide layer 20A / an adhesive layer AD / a non-thermoplastic polyimide layer 20B / a thermoplastic polyimide layer 10B are laminated in this order. Here, the thermoplastic polyimide layer 10A and the non-thermoplastic polyimide layer 20A constitute a first insulating resin layer 40A, and the thermoplastic polyimide layer 10B and the non-thermoplastic polyimide layer 20B constitute a second insulating resin layer 40B. Therefore, the laminate 101 has a structure in which a first insulating resin layer 40A, an adhesive layer AD, and a second insulating resin layer 40B are laminated in this order.
[0067] exist Figure 1 and Figure 2In the structural example shown, the outermost thermoplastic polyimide layer 10A and the thermoplastic polyimide layer 10B have the function of ensuring the adhesion when the metal layer is stacked. The non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B have the function of ensuring dimensional stability. The plurality of thermoplastic polyimide layers 10A, 10B, 30A, and 30B may respectively include the same or different types of thermoplastic polyimide. In addition, the non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B may also include the same or different types of non-thermoplastic polyimide. The details of the preferred polyimide used for the first insulating resin layer 40A and the second insulating resin layer 40B will be described later.
[0068] Furthermore, the first insulating resin layer 40A and the second insulating resin layer 40B may contain, for example, a plasticizer, a hardening resin component such as an epoxy resin, a hardener, a hardening accelerator, an organic filler or an inorganic filler, a coupling agent, a flame retardant, and the like as appropriate.
[0069] <Insulating resin layer>
[0070] The first insulating resin layer 40A and the second insulating resin layer 40B are not limited to a single layer, and a plurality of resin layers may be stacked. The resin constituting the first insulating resin layer 40A and the second insulating resin layer 40B is not particularly limited as long as it is a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenol resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ethylene tetrafluoroethylene (ETFE), etc., preferably including polyimide.
[0071] <Adhesive layer>
[0072] The adhesive layer AD contains a resin component and a filler component.
[0073] Resin composition:
[0074] As a resin component, a polyimide (hereinafter sometimes referred to as "adhesive polyimide") is contained, wherein the polyimide has a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and contains 40 mol% or more of diamine residues derived from a dimer diamine composition relative to all diamine residues, wherein the dimer diamine composition is mainly composed of a dimer diamine in which the two terminal carboxylic acid groups of the dimer acid are substituted with a primary aminomethyl group or an amino group. The details of the adhesive polyimide will be described later. In addition, the resin component also contains a crosslinking agent described later.
[0075] Filling ingredients:
[0076] The filler component contains a metal salt of an organic phosphinic acid. The metal salt of an organic phosphinic acid is a flame retardant that does not reduce the dielectric properties of the polyimide. In order to fully demonstrate the effect of the invention, preferably 80% by weight or more of the filler component, more preferably 90% by weight or more, and most preferably 95% by weight to 100% by weight is a metal salt of an organic phosphinic acid. As the metal salt of an organic phosphinic acid, for example, an aluminum salt of an organic phosphinic acid represented by the following general formula (F1) is preferred.
[0077] [Chemistry 1]
[0078]
[0079] In the general formula (F1), two Rs independently represent an alkyl group. Preferably, R is a lower alkyl group having 1 to 4 carbon atoms.
[0080] The metal salt of an organic phosphinic acid preferably has an average particle size (D 50 ) is within the range of 1.0 μm to 3.0 μm, and the proportion of particles with a diameter exceeding 10 μm is less than 1% by volume. If the proportion of particles with a diameter exceeding 10 μm exceeds 1% by volume, the filler particle size in the bonding layer AD becomes larger, and the filler is easy to fall off during cutting or drilling. As the metal salt of the organic phosphinate as described above, commercial products can be used, for example, Exolit OP945 (trade name, manufactured by Clariant) can be used.
[0081] From the viewpoint of ensuring the flame retardancy of the adhesive layer AD and showing the tensile elastic coefficient and storage elastic coefficient that can suppress the generation of wrinkles during the thermocompression bonding with the insulating resin layer, the weight ratio of the filler component relative to 100 parts by weight of the total amount of the resin component is within the range of more than 40 parts by weight and less than 90 parts by weight, preferably more than 40 parts by weight and less than 80 parts by weight, and more preferably within the range of 45 parts by weight to 70 parts by weight. When the weight ratio of the filler component is less than 40 parts by weight, not only the flame retardant effect cannot be fully exerted, but also wrinkles are easily generated during the thermocompression bonding with the insulating resin layer. If it exceeds 90 parts by weight, the elongation of the adhesive layer AD may be reduced or the dielectric properties may be deteriorated.
[0082] In addition, when the concentration of the filler component of microparticle is improved in order to improve flame retardancy, cohesion will be produced, so a large amount of dispersants need to be allocated.But, because dispersant causes adverse effects on dielectric properties, it is difficult to take into account the raising of low dielectric loss tangent and flame retardancy so far.In the present invention, in the process of manufacturing adhesive resin composition as described later, by implementing the mixing of polyimide and filler component in multiple stages, the high concentration allocation of the filler component exceeding 40 weight parts is realized relative to the total amount 100 weight parts of resin composition without using dispersant.
[0083] In addition, from the viewpoint of fully expressing the effect of the invention, the total amount of the resin component and the filler component is preferably 80 wt % or more, more preferably 90 wt % or more, and most preferably 95 wt % to 100 wt % relative to the total solid content in the adhesive layer AD. In addition, the so-called "solid content" in the present invention refers to the remaining part excluding the solvent.
[0084] In addition, in the bonding layer AD, within the surface field of 100μm×100μm when the thickness-direction section is observed by scanning electron microscopy, the total area ratio of the filler component with a particle diameter exceeding 10μm and the filler detachment portion with a major diameter exceeding 10μm is preferably 1% or less, more preferably 0.5% or less, and most preferably 0.1% to 0% as the average value of the surface field of any ten locations. In the above case, the so-called "particle diameter" refers to the major diameter (the largest diameter) when the plane shape in the scanning electron microscopy observation is other than a perfect circle. In addition, regarding the "filler detachment portion", in the scanning electron microscopy observation of the thickness-direction section, it is observed as a trace of the detachment of the filler component with a particle diameter exceeding 10μm, that is, a void, and the major diameter of the void exceeds 10μm. If the total area ratio of the filler component as coarse particles with a particle size exceeding 10 μm and the filler detachment portion with a long diameter exceeding 10 μm exceeds 1% on average, the filler component is likely to fall off or has already fallen off, so there is a concern that foreign matter may be generated in the circuit processing step or that poor through-hole plating may occur during drilling and hole opening processing.
[0085] The bonding layer AD preferably uses a bonding layer having desired characteristics such as low dielectric loss tangent in addition to having adhesion. For example, in the case of being applied to a circuit substrate, in order to suppress the degradation of dielectric loss, the dielectric loss tangent at 10 GHz in the bonding layer AD is preferably 0.003 or less, more preferably 0.0027 or less, and further preferably 0.0025 or less under humidity conditions, and preferably 0.007 or less, more preferably 0.006 or less, and further preferably 0.005 or less under water absorption conditions. If the dielectric loss tangent at 10 GHz of the bonding layer AD exceeds 0.003 under humidity conditions, when applied to a circuit substrate, it is easy to cause undesirable conditions such as loss of electrical signals on the transmission path of high-frequency signals. In addition, if the dielectric loss tangent at 10 GHz of the bonding layer AD exceeds 0.007 under water absorption conditions, it is easily affected by the ambient humidity and easily generates transmission loss according to the use environment when applied to the circuit substrate. The humidity control conditions and water absorption conditions refer to the conditions of “humidity control” and “water absorption” described in the Examples described later.
[0086] In addition, for example, when applied to a circuit substrate, in order to ensure impedance matching, the relative dielectric constant of the adhesive layer AD at 10 GHz is preferably 4.0 or less. If the relative dielectric constant of the adhesive layer AD at 10 GHz exceeds 4.0, the dielectric loss of the adhesive layer AD will deteriorate when applied to a circuit substrate, and it is easy to cause disadvantages such as loss of electrical signals in the transmission path of high-frequency signals.
[0087] The average thermal expansion coefficient of the adhesive layer AD in the in-plane direction perpendicular to the thickness direction from 250°C to 100°C may exceed 30 ppm / K. Since the adhesive layer AD has low elasticity, even if the average thermal expansion coefficient in the in-plane direction exceeds 30 ppm / K, the internal stress generated during lamination can be alleviated.
[0088] From the viewpoint of effectively suppressing the generation of wrinkles during thermocompression bonding with the insulating resin layer, the tensile elastic coefficient of the adhesive layer AD is preferably in the range of 1.0 GPa to 1.2 GPa, and more preferably in the range of 1.0 GPa to 1.1 GPa. If the tensile elastic coefficient of the adhesive layer AD is less than 1.0 GPa, wrinkles are easily generated during thermocompression bonding with the insulating resin layer. If it exceeds 1.2 GPa, the adhesion with the insulating resin layer is reduced, and bubbles are easily introduced between the insulating resin layer and the adhesive layer AD.
[0089] Similarly, from the viewpoint of effectively suppressing the generation of wrinkles during thermocompression bonding with the insulating resin layer, the storage elastic coefficient of the adhesive layer AD at 80° C. is preferably in the range of 10 MPa to 20 MPa, and more preferably in the range of 13 MPa to 17 MPa. The temperature of 80° C. is a temperature assumed for thermocompression bonding. If the storage elastic coefficient of the adhesive layer AD at the temperature is less than 10 MPa, wrinkles are easily generated during thermocompression bonding with the insulating resin layer. If it exceeds 20 MPa, the adhesion is reduced.
[0090] <Layer thickness>
[0091] In the laminate 100 and the laminate 101, when the total thickness of the first insulating resin layer 40A, the adhesive layer AD, and the second insulating resin layer 40B is set to T1, the total thickness T1 is in the range of 70 μm to 500 μm, preferably in the range of 100 μm to 300 μm. When the total thickness T1 is less than 70 μm, the effect of reducing the transmission loss when the circuit substrate is made is not sufficient, and if it exceeds 500 μm, there is a concern that productivity is reduced. In addition, a thickness of more than 70 μm is difficult to achieve in a single layer, but in the laminate 100 and the laminate 101, the thickness is achieved by a characteristic laminate structure.
[0092] In addition, the thickness T2 of the bonding layer AD is greater than 50 μm. The effect of the present invention that combines excellent dielectric properties and flame retardancy is particularly effectively exerted in a laminated structure in which the thickness T2 of the bonding layer AD with low dielectric loss tangent is large. From the above viewpoint, the thickness T2 of the bonding layer AD is, for example, in the range of more than 50 μm to 450 μm, and more preferably in the range of more than 50 μm to 250 μm. If the thickness T2 of the bonding layer AD is less than the lower limit value, problems such as insufficient low dielectric loss tangent and inability to obtain sufficient dielectric properties may sometimes occur. On the other hand, if the thickness T2 of the bonding layer AD exceeds the upper limit value, undesirable situations such as difficulty in ensuring flame retardancy and reduced dimensional stability may sometimes occur.
[0093] In addition, the effect of the present invention that combines excellent dielectric properties and flame retardancy is particularly effective in a laminated structure in which the ratio of the thickness T2 of the bonding layer AD is large, so the ratio (T2 / T1) of the thickness T2 of the bonding layer AD to the total thickness T1 is preferably in the range of more than 0.5 to 0.96, and more preferably in the range of more than 0.5 to 0.75. When the ratio (T2 / T1) is less than 0.5, the low dielectric loss tangent becomes insufficient and sufficient dielectric properties cannot be obtained. If it exceeds 0.96, it will be difficult to ensure flame retardancy and reduce dimensional stability.
[0094] The thickness T3 of the first insulating resin layer 40A and the second insulating resin layer 40B is preferably in the range of, for example, 10 μm to 50 μm, more preferably in the range of 12 μm to 25 μm. If the thickness T3 of each of the first insulating resin layer 40A and the second insulating resin layer 40B is less than the lower limit, problems such as warping of the laminate 100 and the laminate 101 may occur. If the thickness T3 of the first insulating resin layer 40A and the second insulating resin layer 40B exceeds the upper limit, problems such as reduced transmission characteristics when the circuit substrate is made may occur. In addition, the first insulating resin layer 40A and the second insulating resin layer 40B may have the same thickness or different thicknesses. In addition, the thermoplastic polyimide layer 10A, the thermoplastic polyimide layer 10B, the thermoplastic polyimide layer 30A, and the thermoplastic polyimide layer 30B may have the same thickness or different thicknesses, and the non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B may have the same thickness or different thicknesses.
[0095] <Dielectric loss tangent>
[0096] For example, in the case of being applied to a circuit substrate, in order to suppress the degradation of dielectric loss, the dielectric loss tangent at 10GHz measured by using a split post dielectric resonator (split post dielectric resonators, SPDR) in the laminate 100 and laminate 101 is preferably 0.005 or less, more preferably 0.004 or less, and further preferably 0.003 or less, and preferably 0.008 or less, more preferably 0.007 or less, and further preferably 0.006 or less under water absorption conditions. If the dielectric loss tangent at 10GHz of the laminate 100 and laminate 101 exceeds 0.005 under humidity control conditions, when applied to the circuit substrate, it is easy to produce the undesirable conditions such as the loss of electrical signals on the transmission path of the high-frequency signal. In addition, if the dielectric loss tangent at 10GHz of the laminate 100 and laminate 101 exceeds 0.008 under water absorption conditions, it is easily affected by the influence of environmental humidity, and transmission loss is easily generated according to the use environment when applied to the circuit substrate. The humidity control conditions and water absorption conditions refer to the conditions of “humidity control” and “water absorption” described in the Examples described later.
[0097] <Relative dielectric constant>
[0098] For example, when used as an insulating layer of a circuit board, in order to ensure impedance matching, the laminate 100, 101 preferably has a relative dielectric constant of 3.5 or less at 10 GHz measured using an SPDR as the insulating layer as a whole. If the relative dielectric constant of the laminate 100, 101 at 10 GHz exceeds 3.5, when used in a circuit board, the dielectric loss of the first insulating resin layer 40A and the second insulating resin layer 40B is deteriorated, and it is easy to cause disadvantages such as loss of electrical signals in the transmission path of high-frequency signals.
[0099] The length L of the laminate 100 and the laminate 101 in the width direction (TD direction) is preferably TD The length L in the longitudinal direction (machine direction, MD) is within the range of 0.2 m to 2.0 m. MD The length L in the width direction (TD direction) TD The ratio (L MD / L TD ) is, for example, 25 or more, preferably in the range of 50 to 5000. The laminate 100 and the laminate 101 are in the shape of strips, so that the effect of suppressing uneven thickness and wrinkles that are easily generated when manufacturing by roll-to-roll method can be maximized.
[0100] <Polyimide>
[0101] Next, polyimide, which is a preferred resin constituting the first insulating resin layer 40A, the second insulating resin layer 40B, and the adhesive layer AD, is described. Polyimide is obtained by reacting a tetracarboxylic anhydride component with a diamine component including an aliphatic diamine and / or an aromatic diamine, and contains a tetracarboxylic acid residue derived from the tetracarboxylic anhydride component and a diamine residue derived from the diamine component. In the present invention, the so-called "tetracarboxylic acid residue" means a tetravalent group derived from tetracarboxylic dianhydride, and the so-called "diamine residue" means a divalent group derived from a diamine compound. When the tetracarboxylic dianhydride and the diamine compound as raw materials are reacted in approximately equimolar amounts, the types and molar ratios of the tetracarboxylic acid residues and the diamine residues contained in the polyimide can be made to roughly correspond to the types and molar ratios of the raw materials.
[0102] In addition, in the present invention, the term "polyimide" refers to a resin containing a polymer having an imide group in its molecular structure, such as polyamide-imide, polyether-imide, polyester-imide, polysiloxane-imide, and polybenzimidazole-imide, in addition to polyimide. In addition, when the polyimide has a plurality of structural units, they may exist in a block form or randomly, but preferably randomly.
[0103] The so-called "thermoplastic polyimide" is generally a polyimide whose glass transition temperature (Tg) can be clearly confirmed. In the present invention, it means a polyimide having a storage elastic modulus of 1.0×10 at 30°C measured by a dynamic viscoelasticity measuring device (dynamic thermomechanical analyzer (DMA)). 8 Pa or more, and the storage elastic modulus at 300°C is less than 3.0×10 7 In addition, the so-called "non-thermoplastic polyimide" is a polyimide that does not show softening and adhesiveness even when heated. In the present invention, it means a polyimide having a storage elastic modulus of 1.0×10 at 30°C measured by a dynamic viscoelasticity measuring device (DMA). 9 Pa and the storage elastic coefficient at 300°C is 3.0×10 8 Pa or more polyimide.
[0104] <Thermoplastic polyimide>
[0105] The thermoplastic polyimide used to form the thermoplastic polyimide layer 10A, the thermoplastic polyimide layer 10B, the thermoplastic polyimide layer 30A, and the thermoplastic polyimide layer 30B in the first insulating resin layer 40A and the second insulating resin layer 40B can be controlled in terms of thermal expansion, adhesion, glass transition temperature, etc. by selecting the types of tetracarboxylic anhydride components and diamine components as raw materials, or the molar ratio of each when two or more acid anhydrides or diamines are used. As for the tetracarboxylic anhydride components and diamine components as raw materials, monomers generally used in the synthesis of thermoplastic polyimide can be used, but in order to improve flame retardancy, it is preferable to use aromatic tetracarboxylic dianhydride or aromatic diamine.
[0106] As the aromatic tetracarboxylic dianhydride, for example, pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic dianhydride (ODPA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (D ... anhydride, 6FDA), 2,2-bis〔4-(3,4-dicarboxyphenoxy)phenyl〕propane dianhydride (BPADA), p-phenylene bis(trimellitic acid monoester anhydride) (TAHQ), ethylene glycol bistrimellitic anhydride (TMEG), 2,3,6,7-naphthalene tetracarboxylic dianhydride (NTCDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (3,3',4,4'-biphenyltetracarboxylic Aromatic tetracarboxylic dianhydrides include 2,3',3,4'-biphenyltetracarboxylic dianhydride and 2,2',3,3'-biphenyltetracarboxylic dianhydride.
[0107] In order to impart sufficient flame retardancy to the laminate 100 and the laminate 101, the thermoplastic polyimide layer 30A and the thermoplastic polyimide layer 30B preferably contain tetracarboxylic acid residues derived from one or more of the aromatic tetracarboxylic dianhydrides in a total range of 50 to 100 mol parts, more preferably in a range of 60 to 100 mol parts, relative to 100 mol parts of all tetracarboxylic acid residues.
[0108] As the aromatic diamine, for example, 1,4-diaminobenzene (p-PDA (p-phenylenediamine, p-phenylenediamine)), 1,3-bis(4-aminophenoxy)benzene (1,3-bis(4-aminophenoxy)benzene, TPE-R), 1,3-bis(3-aminophenoxy)benzene (1,3-bis(3-aminophenoxy)benzene, APB), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane, BAPP), bis[4-(4-aminophenoxy)phenyl]ether (bis[4-(4-aminophenoxy)phenyl]ether, BAPE), bis[4-(4-aminophenoxy)phenyl]ether (bis[4-(4-aminophenoxy)phenyl]ether, ... [4-(4-aminophenoxy)phenyl]sulfone (BAPS), bis[4-(4-aminophenoxy)phenyl]ketone (BAPK), bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, bisaniline fluorene, BAFL), 9,9-bis(4-amino-3-chlorophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-fluorophenyl)fluorene, 4,4"-diamino-p-terphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-diethyl ... m-EB), 2,2'-diethoxyl-4,4'-diaminobiphenyl (m-EOB), 2,2'-dipropoxy-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-NP ...di-n-propyl-4,4'-diaminobiphenyl (m-NPB), 2,2'-di-di-n-propyl-4,4'-diaminobiphenyl (m-NPB), 2,2'-di-di-n-propyl-4,4'-diAromatic diamines such as 2'-divinyl-4,4'-diaminobiphenyl (VAB), 4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB), 4,4'-diamino-2,2',5,5'-tetrachlorobiphenyl, and 4,4'-diaminooctafluorobiphenyl.
[0109] In order to impart sufficient flame retardancy to the laminate 100 and the laminate 101, the thermoplastic polyimide layer 10A, the thermoplastic polyimide layer 10B, the thermoplastic polyimide layer 30A, and the thermoplastic polyimide layer 30B preferably contain diamine residues derived from one or more of the aromatic diamines in a total range of 50 to 100 mol parts, more preferably in a range of 60 to 100 mol parts, relative to 100 mol parts of all diamine residues.
[0110] <Non-thermoplastic polyimide>
[0111] The non-thermoplastic polyimide used to form the non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B in the first insulating resin layer 40A and the second insulating resin layer 40B can be controlled in thermal expansion, dielectric properties, etc. by selecting the types of tetracarboxylic anhydride components and diamine components as raw materials, or the molar ratio of each when two or more acid anhydrides or diamines are used. Regarding the tetracarboxylic anhydride components and diamine components as raw materials, monomers generally used in the synthesis of non-thermoplastic polyimide can be used, but in order to improve flame retardancy, it is preferred to use aromatic tetracarboxylic dianhydride or aromatic diamine exemplified in the description of the thermoplastic polyimide.
[0112] In addition, in order to impart sufficient flame retardancy to the laminate 100 and the laminate 101, the non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B preferably contain tetracarboxylic acid residues derived from one or more aromatic tetracarboxylic dianhydrides exemplified in the description of the thermoplastic polyimide in a total amount ranging from 50 to 100 mol parts, more preferably ranging from 60 to 100 mol parts, relative to 100 mol parts of all tetracarboxylic acid residues.
[0113] Furthermore, in order to impart sufficient flame retardancy to the laminate 100 and the laminate 101, the non-thermoplastic polyimide layer 20A and the non-thermoplastic polyimide layer 20B preferably contain a diamine residue derived from one or more of the aromatic diamines exemplified in the description of the thermoplastic polyimide in a total range of 50 to 100 mol parts, more preferably 60 to 100 mol parts, relative to 100 mol parts of all diamine residues.
[0114] <Adhesive polyimide>
[0115] The adhesive polyimide is the main component of the resin component contained in the adhesive layer AD. The so-called main component of the resin component refers to the component contained in excess of 50% by weight relative to all the resin components. In order to fully demonstrate the effect of the invention, the resin component preferably contains 70% by weight or more, more preferably 80% by weight or more, and most preferably 90% by weight or more of the adhesive polyimide.
[0116] (Tetracarboxylic acid residue)
[0117] The adhesive polyimide may contain a tetracarboxylic acid residue derived from a tetracarboxylic acid dianhydride generally used in a thermoplastic polyimide without particular limitation, but preferably contains a total of 90 or more mol parts of tetracarboxylic acid residues derived from a tetracarboxylic acid dianhydride represented by the following general formula (1) (hereinafter, sometimes referred to as "tetracarboxylic acid residue (1)") relative to 100 mol parts of all tetracarboxylic acid residues, and more preferably contains 95 or more mol parts. By containing a total of 90 or more mol parts of tetracarboxylic acid residues (1) relative to 100 mol parts of all tetracarboxylic acid residues, it is easy to achieve a balance between the flexibility and heat resistance of the adhesive polyimide and it is preferred. When the total amount of the tetracarboxylic acid residue (1) is less than 90 mol parts, there is a tendency for the solvent solubility of the adhesive polyimide to decrease.
[0118] [Chemistry 2]
[0119]
[0120] In the general formula (1), X represents a single bond or a divalent group selected from the following formulae.
[0121] [Chemistry 3]
[0122] -CO-, -SO2-, -O-,
[0123]
[0124] -COO- or -COO-Z-OCO-
[0125] In the above formula, Z represents -C6H4-, -(CH2)n- or -CH2-CH(-OC(=O)-CH3)-CH2-, and n represents an integer of 1 to 20.
[0126] Examples of the tetracarboxylic dianhydride from which the tetracarboxylic acid residue (1) is derived include 3,3′,4,4′-biphenyltetracarboxylic dianhydride (BPDA), 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA), 3,3′,4,4′-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4′-oxydiphthalic anhydride (ODPA), 4,4′-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester anhydride) (TAHQ), and ethylene glycol bis(trimellitic acid anhydride) (TMEG).
[0127] The adhesive polyimide may contain a tetracarboxylic acid residue derived from an acid dianhydride other than the tetracarboxylic dianhydride represented by the general formula (1) within a range that does not impair the effects of the invention. Such a tetracarboxylic acid residue is not particularly limited, but preferably, an aromatic tetracarboxylic dianhydride exemplified in the description of the thermoplastic polyimide is used.
[0128] (Diamine residue)
[0129] The adhesive polyimide contains more than 40 mol% of diamine residues derived from a dimer diamine composition relative to all diamine residues, and the dimer diamine composition is mainly composed of a dimer diamine in which the two terminal carboxylic acid groups of dimer acid are substituted with primary aminomethyl or amino groups. When the content of diamine residues derived from the dimer diamine composition is less than 40 mol% relative to all diamine residues, the relative dielectric constant and dielectric loss tangent are easily increased due to the relative increase of polar groups contained in the adhesive polyimide, and the low dielectric loss tangent of the adhesive layer AD becomes difficult, and the adhesiveness required for the adhesive layer AD cannot be obtained. By setting the content of diamine residues derived from the dimer diamine composition to more than 40 mol%, the relative dielectric constant and dielectric loss tangent of the adhesive layer AD can be fully reduced, and the adhesive polyimide can be made solvent soluble. From this viewpoint, the content of the diamine residue derived from the dimer diamine composition is preferably 60 mol% or more, more preferably 80 mol% or more, and most preferably in the range of 90 mol% to 100 mol% based on all diamine residues.
[0130] The dimer diamine composition is a purified product containing the following component (a) as a main component and in which the amounts of the component (b) and the component (c) are controlled.
[0131] (a) dimer diamine;
[0132] The dimer diamine of the component (a) refers to a diamine in which the two terminal carboxylic acid groups (-COOH) of the dimer acid are substituted with primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids. Its industrial production process has been roughly standardized in the industry, and it can be obtained by dimerizing unsaturated fatty acids with carbon numbers of 11 to 22 using clay catalysts, etc. Regarding the dimer acid obtained industrially, the main component is a dibasic acid with a carbon number of 36 obtained by dimerizing unsaturated fatty acids with a carbon number of 18 such as oleic acid, linoleic acid, and linolenic acid, but it contains any amount of monomer acid (carbon number 18), trimer acid (carbon number 54), and other polymerized fatty acids with carbon numbers of 20 to 54 depending on the degree of purification. In addition, after the dimerization reaction, double bonds remain, but in the present invention, it is assumed that the dimer acid also contains compounds that are further hydrogenated to reduce the unsaturation. The dimer diamine of the component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having a carbon number in the range of 18 to 54, preferably in the range of 22 to 44, with a primary aminomethyl group or an amino group.
[0133] As a feature of dimer diamine, the characteristics of the skeleton derived from dimer acid can be given. That is, dimer diamine is a macromolecular aliphatic with a molecular weight of about 560 to 620, so the molar volume of the molecule can be increased, and the polar group of the polyimide can be relatively reduced. It is believed that the characteristics of such dimer diamine help to suppress the reduction of the heat resistance of the adhesive polyimide, while reducing the relative dielectric constant and the dielectric loss tangent to improve the dielectric properties. In addition, due to containing two freely movable hydrophobic chains of 7 to 9 carbon numbers and two chain aliphatic amino groups with a length close to 18 carbon numbers, it is not only possible to provide flexibility to the polyimide, but also the polyimide can be set to an asymmetric chemical structure or a non-planar chemical structure, so it is believed that the low dielectric constant of the polyimide can be achieved.
[0134] The dimer diamine composition preferably uses a material in which the dimer diamine content of the component (a) is increased to 96% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more by a purification method such as molecular distillation. By setting the dimer diamine content of the component (a) to 96% by weight or more, the expansion of the molecular weight distribution of the polyimide can be suppressed. In addition, if technically feasible, it is most preferable that the dimer diamine composition is entirely (100% by weight) composed of the dimer diamine of the component (a).
[0135] (b) a monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having a carbon number in the range of 10 to 40 with a primary aminomethyl group or an amino group;
[0136] The monoacid compound having a carbon number in the range of 10 to 40 is a mixture of a monounsaturated fatty acid having a carbon number in the range of 10 to 20 derived from a raw material of dimer acid and a monoacid compound having a carbon number in the range of 21 to 40, which is a byproduct when producing dimer acid. The monoamine compound is a compound obtained by substituting the terminal carboxylic acid group of these monoacid compounds with a primary aminomethyl group or an amino group.
[0137] The monoamine compound of component (b) is a component that suppresses the increase in molecular weight of polyimide. During the polymerization of polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal anhydride group of polyamic acid or polyimide, thereby sealing the terminal anhydride group and suppressing the increase in molecular weight of polyamic acid or polyimide.
[0138] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polyacid compound having a hydrocarbon group and having a carbon number in the range of 41 to 80 with a primary aminomethyl group or an amino group (except the dimer diamine);
[0139] The polybasic acid compound having a hydrocarbon group with a carbon number in the range of 41 to 80 is a polybasic acid compound having as a main component a tribasic acid compound with a carbon number in the range of 41 to 80, which is a byproduct when producing dimer acid. In addition, it may also contain a polymerized fatty acid other than the dimer acid with a carbon number of 41 to 80. The amine compound is a compound obtained by substituting the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.
[0140] The amine compound of component (c) is a component that promotes the increase in the molecular weight of polyimide. The triamine body derived from trimer acid as the main component of the trifunctional or higher amino group reacts with the terminal anhydride group of polyamic acid or polyimide to increase the molecular weight of the polyimide sharply. In addition, the amine compound derived from the polymerized fatty acid other than the dimer acid having 41 to 80 carbon atoms also increases the molecular weight of the polyimide and becomes the cause of the gelation of the polyamic acid or polyimide.
[0141] When each component is quantitatively determined by using gel permeation chromatography (GPC), in order to easily confirm the peak start, peak top and peak end of each component of the dimer diamine composition, a sample obtained by treating the dimer diamine composition with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard substance. Using the sample prepared as described above, each component is quantitatively determined using the area percentage of the chromatogram of GPC. The peak start and peak end of each component are set to the minimum value of each peak curve, and the area percentage of the chromatogram can be calculated based on this.
[0142] In addition, the dimer diamine composition preferably contains components (b) and (c) in an area percentage of a chromatogram obtained by GPC measurement, and the total content is preferably 4% or less, and preferably less than 4%. By setting the total content of components (b) and (c) to 4% or less, the expansion of the molecular weight distribution of the polyimide can be suppressed.
[0143] In addition, the area percentage of the chromatogram of the component (b) is preferably 3% or less, more preferably 2% or less, and further preferably 1% or less. By setting it to such a range, the decrease in the molecular weight of the polyimide can be suppressed, and the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component can be expanded. In addition, the component (b) may not be included in the dimer diamine composition.
[0144] In addition, the area percentage of the chromatogram of the component (c) is preferably 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it to such a range, the rapid increase in the molecular weight of the polyimide can be suppressed, and the rise in the dielectric loss tangent under the wide frequency of the resin film can be suppressed. In addition, the component (c) may not be included in the dimer diamine composition.
[0145] In addition, when the ratio (b / c) of the area percentage of the chromatogram of component (b) and component (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and less than 1.0. By setting such a molar ratio, it is easier to control the molecular weight of the polyimide.
[0146] In addition, when the ratio (b / c) of the area percentage of the chromatogram of component (b) and component (c) is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and 1.1 or less. By setting such a molar ratio, it is easier to control the molecular weight of the polyimide.
[0147] The dimer diamine composition can utilize commercial products, preferably for the purpose of reducing the components other than the dimer diamine of component (a) for purification, for example, preferably component (a) is set to 96% by weight or more. As a purification method, there is no particular limitation, preferably a known method such as distillation or precipitation purification. As a commercial product, for example, PRIAMINE 1073 (trade name) manufactured by Croda Japan, PRIAMINE 1074 (trade name) manufactured by Croda Japan, PRIAMINE 1075 (trade name) manufactured by Croda Japan, etc.
[0148] The adhesive polyimide may contain a diamine residue derived from a diamine component other than the above. Such a diamine residue is not particularly limited, but is preferably a diamine residue derived from the aromatic diamine exemplified in the description of the thermoplastic polyimide.
[0149] The adhesive polyimide preferably has a weight average molecular weight (Mw) in the range of 25,000 to 100,000. By setting Mw to more than 25,000, the tear strength and adhesive strength when the film is made can be improved, and the storage stability of the varnish can be improved. When Mw is less than 25,000, the film becomes brittle. In a film containing a metal salt of an organic phosphinate as a filler component at a high concentration, stress is generated at the interface between the filler and the resin when bent or stretched, thus causing fracture or causing voids at the interface between the filler and the resin. On the other hand, when Mw exceeds 100,000, the viscosity of the varnish rises and operability is easily reduced. In addition, the lower the molecular weight of Mw within the range, the narrower the molecular weight distribution tends to be, so the more preferred range of Mw is in the range of 50,000 to 100,000, and further preferably in the range of 50,000 to 70,000.
[0150] The imide group concentration of the adhesive polyimide is preferably 22% by weight or less, more preferably 20% by weight or less. Here, "imide group concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire structure of the polyimide. If the imide group concentration exceeds 22% by weight, the molecular weight of the resin itself becomes smaller, and the low hygroscopicity is also deteriorated due to the increase of polar groups, and the Tg and elastic coefficient increase.
[0151] The adhesive polyimide is most preferably a fully imidized structure. Part of the polyimide may also be an amic acid. The imidization rate can be measured by using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) and using a single reflection ATR (attenuated total reflectance) method to measure the infrared absorption spectrum of the polyimide film at 1015 cm -1 Based on the benzene ring absorber nearby, according to 1780cm -1 The absorbance derived from the stretching of C=O of the imide group was calculated.
[0152] (Cross-linking formation of adhesive polyimide)
[0153] When the adhesive polyimide has a ketone group, a cross-linking agent having a functional group that reacts nucleophilically with the ketone group is reacted to form a cross-linked structure. By forming a cross-linked structure, heat resistance can be improved. This polyimide (hereinafter sometimes referred to as "cross-linked polyimide") that forms a cross-linked structure is an application example of adhesive polyimide and becomes a preferred form. In addition, since the weight average molecular weight varies greatly with cross-linking, the adhesive polyimide before cross-linking formation satisfies the weight average molecular weight.
[0154] As a crosslinking agent, it is preferred to use an amino compound having at least two primary amino groups as functional groups (hereinafter sometimes referred to as "amino compound for crosslinking formation"). A crosslinking structure can be formed by reacting the ketone group of the adhesive polyimide with the amino group of the amino compound for crosslinking formation to form a C=N bond. That is, the two primary amino groups in the amino compound function as functional groups that react nucleophilically with the ketone group. The primary amino group is not accompanied by the generation of a hydroxyl group (-OH) that deteriorates the dielectric properties, so it is particularly advantageous.
[0155] As a preferred tetracarboxylic dianhydride for forming an adhesive polyimide having a ketone group, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) can be cited, and as a diamine compound, for example, aromatic diamines such as 4,4'-bis(3-aminophenoxy)benzophenone (4,4'-bis(3-aminophenoxy)benzophenone, BABP) and 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, BABB) can be cited. For the purpose of forming a crosslinked structure, it is particularly preferred to allow an amino compound for crosslinking formation to act on the adhesive polyimide, and the adhesive polyimide contains preferably 50 mol% or more, more preferably 60 mol% or more of BTDA residues derived from BTDA relative to all tetracarboxylic acid residues. In addition, in the present invention, the so-called "BTDA residue" refers to a tetravalent group derived from BTDA.
[0156] As the amino compound for crosslinking formation, there can be exemplified: (I) dihydrazide compounds, (II) aromatic diamines, (III) aliphatic amines, etc. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds are easy to form a crosslinked structure even at room temperature, which may cause concerns about the storage stability of the varnish. On the other hand, aromatic diamines need to be set to a high temperature in order to form a crosslinked structure. As described above, when a dihydrazide compound is used, both the storage stability of the varnish and the shortening of the curing time can be taken into account. As the dihydrazide compound, for example, dihydrazide compounds such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglycolic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4-diphenyl dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine dihydrazide, and itaconic acid dihydrazide are preferred. The above dihydrazide compounds may be used alone or in combination of two or more.
[0157] Furthermore, the amino compounds (I) dihydrazide compounds, (II) aromatic diamines, (III) aliphatic amines, etc. may be used in combination of two or more, for example, a combination of (I) and (II), a combination of (I) and (III), or a combination of (I) and (II) and (III).
[0158] In addition, from the viewpoint of making the network structure formed by crosslinking using the crosslinking amino compound more dense, the molecular weight of the crosslinking amino compound used in the present invention (the weight average molecular weight when the crosslinking amino compound is an oligomer) is preferably 5,000 or less, more preferably 90 to 2,000, and further preferably 100 to 1,500. Among them, a crosslinking amino compound having a molecular weight of 100 to 1,000 is particularly preferred. If the molecular weight of the crosslinking amino compound is less than 90, one amino group of the crosslinking amino compound is limited to forming a C=N bond with the ketone group of the adhesive polyimide, and the surrounding of the remaining amino group becomes sterically bulky, so that it tends to be difficult for the remaining amino group to form a C=N bond.
[0159] When the ketone group in the adhesive polyimide is cross-linked with the cross-linking amino compound, the cross-linking amino compound is added to the resin solution containing the adhesive polyimide to cause the ketone group in the adhesive polyimide to undergo a condensation reaction with the primary amino group of the cross-linking amino compound. The resin solution is cured by the condensation reaction to become a cured product.
[0160] The ketone group in the adhesive polyimide is cross-linked by a nucleophilic reaction with the functional group of the cross-linking agent to form a cross-linked polyimide as a cured product. The conditions for the nucleophilic reaction for cross-linking are not particularly limited and can be selected according to the type of cross-linking agent. For example, when the primary amino group of the cross-linking amino compound is reacted with the ketone group in the adhesive polyimide, an imide bond (C=N bond) is generated by a condensation reaction using heating to form a cross-linked structure. The conditions for the condensation reaction for cross-linking are not particularly limited if the ketone group in the adhesive polyimide forms an imide bond (C=N bond) with the primary amino group of the cross-linking amino compound. Regarding the temperature of the heating condensation, for example, it is preferably in the range of 120°C to 220°C, and more preferably in the range of 140°C to 200°C, for the purpose of releasing the water generated by the condensation to the outside of the system, or for simplifying the condensation process when the heating condensation reaction is performed after the synthesis of the adhesive polyimide. The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be determined, for example, by measuring the infrared absorption spectrum using a Fourier transform infrared spectrophotometer (commercially available product: FT / IR620 manufactured by JASCO Corporation) and using the wavelength at 1670 cm -1 The decrease or disappearance of the absorption peak derived from the ketone group in the polyimide resin near 1635 cm -1 The presence of an absorption peak derived from an imine group in the vicinity of the amine group can be used to confirm the presence of an absorption peak derived from an imine group in the vicinity of the amine group.
[0161] The heat condensation of the ketone group of the adhesive polyimide and the primary amino group of the crosslink-forming amino compound can be performed, for example, by the following method.
[0162] (1) A method in which an amino compound for crosslinking is added immediately after the synthesis (imidization) of an adhesive polyimide and then heated;
[0163] (2) A method in which an excess amount of an amino compound is preliminarily charged as a diamine component, and then the adhesive polyimide is synthesized (imidized), and the remaining amino compound that does not participate in imidization or amidation is used as an amino compound for crosslinking and heated together with the adhesive polyimide;
[0164] or
[0165] (3) A method of heating the adhesive polyimide composition to which the crosslink-forming amino compound is added after processing it into a predetermined shape (for example, after coating it on an arbitrary substrate or forming it into a film).
[0166] In order to impart heat resistance to adhesive polyimide, examples of cross-linked polyimide that forms a cross-linked structure by forming imide bonds are given for explanation, but the invention is not limited to this. As a method for curing polyimide, for example, epoxy resin, epoxy resin hardener, maleimide, activated ester resin, resin having a styrene skeleton, and other compounds having unsaturated bonds can also be formulated for curing.
[0167] By using the above adhesive polyimide, the adhesive layer AD has excellent flexibility and dielectric properties (low dielectric constant and low dielectric loss tangent). In addition, in the adhesive layer AD, in addition to the metal salt of the organic phosphinate, hardening resin components such as plasticizers, epoxy resins, hardeners, hardening accelerators, organic fillers or inorganic fillers, coupling agents, etc. can be appropriately formulated.
[0168] <Synthesis of polyimide>
[0169] The thermoplastic polyimide, non-thermoplastic polyimide and adhesive polyimide constituting the first insulating resin layer 40A and the second insulating resin layer 40B can be manufactured by reacting the tetracarboxylic anhydride component and the diamine component in a solvent, and heating and ring-closing after generating polyamic acid. For example, the tetracarboxylic anhydride component and the diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the polymerization reaction is carried out by stirring for 30 minutes to 24 hours at a temperature in the range of 0°C to 100°C, thereby obtaining a polyamic acid as a precursor of the polyimide. During the reaction, the reaction components are dissolved in a manner such that the generated precursor becomes within a range of 5% by weight to 50% by weight, preferably within a range of 10% by weight to 40% by weight in the organic solvent. As the organic solvent used in the polymerization reaction, for example, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, cresol, etc. It is also possible to use two or more of these solvents, and further, it is also possible to use aromatic hydrocarbons such as xylene and toluene. In addition, there is no particular limitation on the amount of such an organic solvent used, and it is preferably used in an amount adjusted to a concentration of about 5% by weight to 50% by weight of the polyamic acid solution obtained by the polymerization reaction.
[0170] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, but can be concentrated, diluted or replaced with other organic solvents as needed. In addition, polyamic acid is generally excellent in solvent solubility, so it can be advantageously used. The viscosity of the solution of polyamic acid is preferably within the range of 500mPa·s to 100,000mPa·s. If it deviates from the range, it is easy to produce uneven thickness, stripes and other defects on the film, for example, when a coating operation is performed using a coating machine.
[0171] The method of imidizing the polyamic acid to form the adhesive polyimide is not particularly limited, and heat treatment of heating under temperature conditions within a range of 80° C. to 400° C. for 1 to 24 hours can be preferably employed.
[0172] [Metal-clad laminate]
[0173] The metal-clad laminate of the present invention includes the above-mentioned laminate and a metal layer laminated on one surface or both surfaces of the laminate.
[0174] Figure 3 The cross-sectional structure of the metal-clad laminate 200 according to the preferred embodiment of the present invention is shown. The metal-clad laminate 200 has a structure in which a metal layer 110A and a metal layer 110B are laminated on both sides of the laminate 100. Therefore, the metal-clad laminate 200 has a structure in which the metal layer 110A / the first insulating resin layer 40A / the adhesive layer AD / the second insulating resin layer 40B / the metal layer 110B are laminated in this order. The metal layer 110A and the metal layer 110B are respectively located on the outermost sides, and the first insulating resin layer 40A and the second insulating resin layer 40B are arranged inside them, and the adhesive layer AD is arranged between the first insulating resin layer 40A and the second insulating resin layer 40B. The metal-clad laminate 200 having such a layer structure can also be considered to have the following structure, namely, a first single-sided metal-clad laminate (C1) obtained by stacking a metal layer 110A, a thermoplastic polyimide layer 10A, a non-thermoplastic polyimide layer 20A and a thermoplastic polyimide layer 30A in this order and a second single-sided metal-clad laminate (C2) obtained by stacking a metal layer 110B, a thermoplastic polyimide layer 10B, a non-thermoplastic polyimide layer 20B and a thermoplastic polyimide layer 30B in this order, which are bonded together using an adhesive layer AD in a manner such that the insulating resin layer sides face each other.
[0175] In addition, if Figure 4As shown, by using the laminate 101 instead of the laminate 100, a metal-clad laminate 201 having a structure in which the metal layer 110A and the metal layer 110B are laminated on both sides of the laminate 101 can be provided. The metal-clad laminate 201 has a structure in which the metal layer 110A / the first insulating resin layer 40A / the bonding layer AD / the second insulating resin layer 40B / the metal layer 110B are laminated in this order. In the above case, the metal-clad laminate 201 can also be considered to have the following structure, namely, a first single-sided metal-clad laminate (C1) obtained by stacking a metal layer 110A, a thermoplastic polyimide layer 10A and a non-thermoplastic polyimide layer 20A in this order and a second single-sided metal-clad laminate (C2) obtained by stacking a metal layer 110B, a thermoplastic polyimide layer 10B and a non-thermoplastic polyimide layer 20B in this order, which are bonded together using an adhesive layer AD in a manner such that the insulating resin layer sides face each other.
[0176] In addition, Figure 3 and Figure 4 In the figure, a double-sided metal-clad laminate having a metal layer on both sides of the laminate 100 and the laminate 101 is exemplified, but a single-sided metal-clad laminate having a metal layer on one side of the laminate 100 and the laminate 101 may be used.
[0177] (Metal layer)
[0178] The material of the metal layer 110A and the metal layer 110B is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among them, copper or copper alloys are particularly preferred. In addition, the material of the wiring layer in the circuit substrate of the present embodiment described later is also the same as that of the metal layer 110A and the metal layer 110B.
[0179] The thickness of the metal layer 110A and the metal layer 110B is not particularly limited. For example, when a metal foil such as copper foil is used, it is preferably 35 μm or less, and more preferably in the range of 5 μm to 25 μm. From the perspective of production stability and operability, the lower limit of the thickness of the metal foil is preferably set to 5 μm. In addition, when a copper foil is used, it can be a rolled copper foil or an electrolytic copper foil. In addition, as the copper foil, a commercially available copper foil can be used.
[0180] In addition, the metal foil may be subjected to surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, silane coupling agent, etc., for the purpose of rust prevention or improvement of adhesive strength.
[0181] [Manufacturing of Metal-Clad Laminated Plate]
[0182] The metal-clad laminate 200 and the metal-clad laminate 201 can be produced, for example, by the following method 1 or method 2. The adhesive polyimide forming the adhesive layer AD can be formed by cross-linking as described above.
[0183] [Method 1]
[0184] First, a first single-sided metal-clad laminate (C1) and a second single-sided metal-clad laminate (C2) having the layer structure are prepared. Next, a solution containing the adhesive polyimide and a filler component is formed into a sheet to form an adhesive film as an adhesive layer AD. The adhesive film is arranged between the first insulating resin layer 40A of the first single-sided metal-clad laminate (C1) and the second insulating resin layer 40B of the second single-sided metal-clad laminate (C2), and the adhesive film is bonded and thermocompression-bonded.
[0185] [Method 2]
[0186] First, a first single-sided metal-clad laminate (C1) and a second single-sided metal-clad laminate (C2) are prepared. Next, an adhesive resin composition forming an adhesive layer AD is applied to a first insulating resin layer 40A of the first single-sided metal-clad laminate (C1) or a second insulating resin layer 40B of the second single-sided metal-clad laminate (C2) at a predetermined thickness, and dried to form a coating film. Thereafter, the first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2) are bonded and thermocompressed on one side of the coating film.
[0187] The first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2) used in Method 1 and Method 2 can be manufactured, for example, by the following method: repeatedly coating a solution of a polyamide acid which is a precursor of a thermoplastic polyimide or a non-thermoplastic polyimide on the metal foil to be the metal layer 110A and the metal layer 110B in sequence and drying the solution, and then heat-treating the solution to imidize the metal foil.
[0188] In addition, the adhesive film used in method 1 can be manufactured, for example, by coating a solution containing the adhesive polyimide, a filler component, and an organic solvent (sometimes referred to as an "adhesive resin composition" in this specification) on a supporting substrate and drying it, and then peeling it from the supporting substrate to form an adhesive film. In addition, the adhesive film and the adhesive resin composition are also one of the preferred embodiments of the present invention.
[0189] In the above, the method of applying the polyamic acid solution or adhesive resin composition to the metal foil, supporting substrate, insulating resin layer, etc. is not particularly limited, and for example, coating can be performed using a coater such as a notch wheel, a die, a knife, or a die lip.
[0190] The laminated bodies 100 and 101 of the present embodiment obtained as described above can be processed into a circuit board such as a single-sided FPC or a double-sided FPC by etching the metal layer 110A and / or the metal layer 110B to produce a wiring circuit.
[0191] [Adhesive resin composition]
[0192] Next, the adhesive resin composition of the embodiment of the present invention is described. Since the adhesive polyimide is solvent-soluble, it can be used in the form of a composition containing an organic solvent, and can be preferably used as an adhesive resin composition containing a resin component, a filler component and an organic solvent. The contents of the resin component and the filler component are as described. The tensile elastic coefficient of the adhesive resin composition when forming a film with a thickness in the range of more than 50 μm and less than 450 μm is in the range of more than 1.0 GPa and less than 1.2 GPa, and the storage elastic coefficient at 80°C is in the range of more than 10 MPa and less than 20 MPa. The film is the same as the adhesive film described below.
[0193] In the adhesive resin composition, from the viewpoint of ensuring the flame retardancy of the adhesive layer AD and showing the tensile elastic coefficient and storage elastic coefficient that can suppress the generation of wrinkles during the thermal compression bonding with the insulating resin layer, the weight ratio of the filler component relative to the total amount of 100 parts by weight of the resin component is within the range of more than 40 parts by weight and less than 90 parts by weight, preferably more than 40 parts by weight and less than 80 parts by weight, and more preferably within the range of 45 parts by weight to 70 parts by weight. When the weight ratio of the filler component is less than 40 parts by weight, not only can the flame retardant effect not be fully exerted, but wrinkles are easily generated during the thermal compression bonding with the insulating resin layer. If it exceeds 90 parts by weight, the elongation when the adhesive layer AD or the adhesive film is formed is sometimes reduced, or the dielectric properties are deteriorated. In addition, from the viewpoint of fully showing the effect of the invention, the total amount of the resin component and the filler component is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95% by weight to 100% by weight relative to the total solid content in the adhesive resin composition.
[0194] As an organic solvent, there is no particular limitation as long as it can dissolve the adhesive polyimide, and examples thereof include: N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexanone, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, methanol, ethanol, benzyl alcohol, cresol, acetone, etc. These organic solvents may be used in combination of two or more, and aromatic hydrocarbons such as xylene and toluene may also be used in combination.
[0195] In addition, when the adhesive resin composition uses an adhesive polyimide having a ketone group in the molecule as a resin component, it is preferably a crosslinking agent having a functional group that reacts nucleophilically with the ketone group as an arbitrary component. Here, the contents of the adhesive polyimide and the crosslinking agent having a ketone group in the molecule are as described. The adhesive resin composition preferably contains a crosslinking agent in a manner such that the functional groups of the crosslinking agent are in the range of 0.04 mol to 0.50 mol, preferably in the range of 0.06 mol to 0.40 mol, relative to 1 mol of the ketone group contained in the adhesive polyimide. For example, when an amino compound for crosslinking formation is used as a crosslinking agent, the primary amino group can be set to be in the range of 0.04 mol to 0.50 mol, preferably in the range of 0.06 mol to 0.40 mol, relative to 1 mol of the ketone group. When the functional groups of the crosslinking agent are less than 0.04 mol in total relative to 1 mol of the ketone group, crosslinking cannot be fully performed, so there is a tendency to be difficult to show heat resistance after curing. On the other hand, if it exceeds 0.5 mol, there is a tendency to increase the dielectric loss tangent. It is speculated that this is because the mobility of the polyimide molecular chain is limited due to the excessive cross-linking agent, which hinders the formation of a regular structure of the molecular chain that effectively suppresses the dielectric loss tangent during hardening. In addition, if the amount of the cross-linking agent is too much, the unreacted cross-linking agent acts as a thermoplastic agent, which tends to reduce the heat resistance when used as the bonding layer AD.
[0196] The viscosity of the adhesive resin composition is not particularly limited as long as it is a viscosity that can be applied, for example, preferably within the range of 500mPa·s to 100000mPa·s, more preferably within the range of 1000mPa·s to 5000mPa·s. If it deviates from the above range, it is easy to produce uneven thickness, stripes and other defects on the adhesive film during the coating operation. In addition, the solid content concentration in the adhesive resin composition is preferably within the range of 30% by weight to 40% by weight, more preferably within the range of 33% by weight to 37% by weight.
[0197] The adhesive resin composition may contain, as appropriate, plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, organic fillers or inorganic fillers other than metal salts of organic phosphinic acids, coupling agents, dispersants, and the like as optional components within a range that does not impair the effects of the invention.
[0198] The adhesive resin composition can be produced by a method comprising the following steps (i) and (ii);
[0199] (i) a step of obtaining a filler dispersion by mixing a portion of the resin component and the filler component in an organic solvent and stirring the mixture;
[0200] as well as
[0201] (ii) A step of obtaining an adhesive resin composition by mixing the rest of the resin component together with the organic solvent into the filler dispersion and stirring the mixture.
[0202] In step (i), the weight ratio of the resin component in the filler dispersion is set to within the range of 3 to 15 parts by weight relative to 100 parts by weight of the final total amount of the resin component, and the solid content concentration in the filler dispersion is adjusted to within the range of 40% to 60% by weight. When the weight ratio of the resin component in the filler dispersion obtained in step (i) is less than 3 parts by weight relative to 100 parts by weight of the final total amount of the resin component, or when the solid content concentration exceeds 60% by weight, uniform dispersion of the filler component becomes difficult and aggregation occurs. On the other hand, when the weight ratio of the resin component in the filler dispersion obtained in step (i) exceeds 15 parts by weight relative to 100 parts by weight of the final total amount of the resin component, or when the solid content concentration is less than 40% by weight, it is difficult to prepare a high concentration of the filler component exceeding 40 parts by weight in step (ii).
[0203] In step (ii), the weight ratio of the filler component in the adhesive resin composition is adjusted to be more than 40 parts by weight and less than 90 parts by weight relative to 100 parts by weight of the final total amount of the resin component, and the solid content concentration in the adhesive resin composition is adjusted to be within the range of 30% by weight to 40% by weight.
[0204] In addition, as the organic solvent used in the step (i) and the step (ii), the same organic solvent as described for the adhesive resin composition can be used.
[0205] According to the manufacture method of the present embodiment, by multi-stage deployment of resin component and adjusting solid content concentration, no cohesion occurs when dispersant is not deployed, high concentration deployment of filler component exceeding 40 weight parts can be carried out relative to the final total amount of 100 weight parts of resin component, when forming adhesive layer AD or adhesive film, low dielectric loss tangent and flame retardancy improvement are achieved. The adhesive resin composition obtained by the manufacture method of the present embodiment does not need dispersant, so it can be substantially free of dispersant. Wherein, it does not hinder the deployment of dispersant in the range that dielectric properties will not be greatly affected. In addition, so-called "substantially free of dispersant", for example, refers to the amount of less than 1.0 weight parts relative to the minimum dispersant amount, i.e., 1.0 weight parts, required for well dispersing the filler component of 100 weight parts, preferably the amount below 0.1 weight part.
[0206] [Adhesive film]
[0207] Next, the adhesive film of the embodiment of the present invention is described. The adhesive film can be manufactured by applying the adhesive resin composition on any substrate and peeling it off after drying. The adhesive film contains a resin component and a filler component, and the composition of each component is the same as the adhesive layer AD, and the weight ratio of the filler component relative to the total amount of 100 parts by weight of the resin component in the adhesive film is more than 40 parts by weight and is within the range of less than 90 parts by weight. In addition, from the perspective of fully showing the effect of the invention, the total amount of the resin component and the filler component is preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 95% by weight to 100% by weight. In addition, the thickness of the adhesive film is preferably set to the same thickness as the adhesive layer AD in the laminate 100 and the laminate 101, and the tensile elastic coefficient, storage elastic coefficient, dielectric loss tangent under humidity control conditions and relative dielectric constant of the adhesive film at this time are the same as the adhesive layer AD. Furthermore, when the cross section in the thickness direction of the adhesive film is observed by a scanning electron microscope, the total area ratio of the filler component with a particle diameter exceeding 10 μm and the filler falling part with a major diameter exceeding 10 μm within a surface field of 100 μm×100 μm is preferably 1% or less, more preferably 0.5% or less, and most preferably 0.1% to 0% as the average value of the surface field at any ten locations. In the above case, the meanings of "particle diameter" and "filler falling part" are as described in the adhesive layer AD.
[0208] [Circuit board]
[0209] The metal-clad laminate 200 and the metal-clad laminate 201 of the present embodiment are mainly effectively used as circuit substrate materials of FPC, rigid-flexible circuit substrate, etc. That is, by processing one or both of the two metal layers 110A and 110B of the metal-clad laminate 200 and the metal-clad laminate 201 of the present embodiment into a pattern to form a wiring layer by a conventional method, a circuit substrate such as an FPC as an embodiment of the present invention can be manufactured.
[0210] [Electronic components, electronic equipment]
[0211] The electronic components and electronic devices of the present embodiment include the circuit substrate. As the electronic components of the present embodiment, for example, there can be listed: liquid crystal displays, organic electroluminescence (EL) displays, electronic paper and other display devices, organic EL lighting, solar cells, touch screens, camera modules, inverters, converters and their structural components. In addition, as electronic devices, for example, HDDs, DVDs, mobile phones, smart phones, tablet terminals, electronic control units (ECUs) of automobiles, power control units (PCUs), etc. The circuit substrate is preferably used as parts such as wiring of movable parts, or cables, connectors, etc. in these electronic components or electronic devices.
[0212] [Example]
[0213] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. In the following examples, unless otherwise specified, various measurements and evaluations are as follows.
[0214] [Viscosity measurement]
[0215] The viscosity at 25° C. was measured using an E-type viscometer (Brookfield, trade name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value when the viscosity stabilized was read 2 minutes after the start of the measurement.
[0216] [Measurement of weight average molecular weight (Mw)]
[0217] The weight average molecular weight was measured by gel permeation chromatography (manufactured by Tosoh Corporation, trade name: HLC-8220GPC) using polystyrene as a standard substance and tetrahydrofuran (THF) as a developing solvent.
[0218] [Determination of relative dielectric constant (Dk) and dielectric loss tangent (Df)]
[0219] Using a vector network analyzer (manufactured by Agilent, trade name E8363C) and an SPDR resonator, the relative dielectric constant and dielectric loss tangent of the resin sheet at 10 GHz in "humidity adjustment" and "water absorption" were measured. The "humidity adjustment" was measured for 24 hours under the conditions of temperature: 24°C to 26°C and humidity 45%RH to 55%RH, and the "water absorption" was measured after being immersed in pure water for 48 hours at temperature: 24°C to 26°C and humidity 45%RH to 55%RH.
[0220] [Determination of coefficient of thermal expansion (CTE)]
[0221] The adhesive layer peeled off from the single-sided metal-clad laminate or the release substrate was cut into a size of 3 mm × 20 mm, and a thermomechanical analyzer (manufactured by Hitachi High-Tech Science, trade name: TMA7100) was used to increase the temperature from 5°C to 50°C at a constant heating rate while applying a load of 5.0 g, and the average thermal expansion coefficient (thermal expansion coefficient) from 10°C to 20°C was obtained. In addition, a polyimide film was cut into the same size, and the temperature was increased from 30°C to 265°C at a constant heating rate while applying a load of 5.0 g, and then maintained at the temperature for 10 minutes, and then cooled at a rate of 5°C / min, and the average thermal expansion coefficient (thermal expansion coefficient) from 250°C to 100°C was obtained.
[0222] [Determination of storage elastic modulus and glass transition temperature (Tg)]
[0223] Regarding the storage elastic coefficient, the next layer after peeling off from the single-sided metal-clad laminate or the release substrate was cut into a size of 5 mm × 20 mm, and a dynamic viscoelasticity device (DMA: manufactured by TA Instrument, trade name: RSA-G2) was used to step-heat from 30°C to 100°C at a heating rate of 4°C / min, and the measurement was performed at a frequency of 6 Hz to measure the storage elastic coefficient at 80°C as the lamination temperature. In addition, the polyimide film was cut into the same size, and step-heated from 30°C to 400°C at a heating rate of 4°C / min, and the measurement was performed at a frequency of 11 Hz. The maximum temperature at which the value of Tanδ in the measurement was the largest was defined as Tg. In addition, the storage elastic coefficient at 30°C is 1.0×10 8 Pa or more, and the storage elastic modulus at 300°C is less than 3.0×10 7 The polyimide with a storage modulus of 1.0×10 9 Pa, the storage elastic coefficient at 300°C is 3.0×10 8 Polyimides with a viscosity of Pa or more are judged to be "non-thermoplastic".
[0224] [Determination of tensile strength, tensile elongation and tensile elastic modulus]
[0225] The tensile strength, tensile elongation and tensile modulus of elasticity were measured using Strograph R-1 manufactured by Toyo Seiki Seisaku-sho, Ltd. at a temperature of 23°C and a relative humidity of 50%. For the sample used for measurement, the adhesive layer after peeling off from the single-sided metal-clad laminate or the demolding substrate was cut into a size of MD: 250mm×TD: 12.7mm, and the measurement was performed under the conditions of dynamometer: 500N, tensile speed: 50mm / min, and distance between chucks: 50mm. The tensile strength is set to the stress value calculated by dividing the load at the time of sample rupture by the cross-sectional area, and the tensile elongation is set to the value obtained by dividing the strain at the time of sample rupture by the length of the sample in the MD direction. The tensile modulus of elasticity was calculated by the least squares method from the interval of 0.05% to 0.5% strain.
[0226] [Measurement of particle diameter of filler used]
[0227] The particle size was measured by laser diffraction-scattering measurement using a laser diffraction particle size distribution analyzer (Malvern, trade name: Master Sizer 3000) with 2-propanol as the dispersion medium and a particle refractive index of 1.50.
[0228] [Evaluation of flame retardancy]
[0229] Flame retardancy is measured by the following procedure. For metal-clad laminates, a film is obtained by etching away the copper foil using an aqueous solution of ferric chloride, and is set as a flame retardancy evaluation sample (width 50mm×length 180mm). For the flame retardancy evaluation sample, the burning time (t1) after the first flame is removed is measured according to the thin material vertical test method of the UL94VTM test. In addition, the case where the probability of the burning time (t1) of 10 samples being less than 10 seconds exceeds 80% is set as ○ (qualified), and the case where it is less than 80% is set as × (unqualified).
[0230] [Evaluation of uneven thickness]
[0231] The thickness unevenness is measured by the following procedure. For the adhesive layer peeled off from the single-sided metal-clad laminate or the release substrate, the average thickness of the portion excluding the end 30 mm is calculated using a contact digital film thickness meter (DIGIMICRO MH-15 manufactured by Nikon) at intervals of 1 mm in the TD direction. The absolute value of the difference between the thickness of each measurement point excluding the end 30 mm and the average thickness is summed up and divided by the number of measurement points, and the resulting value is taken as the thickness unevenness.
[0232] [Evaluation of wrinkles and adhesion]
[0233] Regarding the evaluation of wrinkles, the double-sided copper-clad laminate after lamination was visually observed to confirm whether there were step-shaped wrinkles caused by deformation or folding of the adhesive layer. In addition, the single-sided copper-clad laminate was peeled off from the double-sided copper-clad laminate after lamination, and the surface of the adhesive layer was visually observed to confirm whether there were changes in color tone caused by deformation or folding of the adhesive layer.
[0234] [Evaluation of filler shedding properties and evaluation of coarse particle ratio]
[0235] Regarding the evaluation of filler shedding properties, a sample obtained by cutting the adhesive layer into a size of MD: 10 mm × TD: 2 mm was used. The sample was cut in the thickness direction at 90 degrees above the plane of the sample using a small microtome (manufactured by Jasco Engineering, HW-1) equipped with a single-edged razor (manufactured by Feather Safety Razor, FAS-10). The cut surface was then observed using a scanning electron microscope (manufactured by Hitachi, Ltd., S-4700) at an accelerating voltage of 5.0 kV to confirm the presence or absence of voids in the cross section of the adhesive layer.
[0236] In addition, in the observation of the cross-section in the thickness direction of the sample using the scanning electron microscope (manufactured by Hitachi, Ltd., S-4700), the total area ratio of coarse filler particles with a particle diameter exceeding 10 μm and filler detachment portions with a long diameter exceeding 10 μm within a surface field of view of 100 μm×100 μm is measured, and the average value of the surface field of view at any ten locations is obtained, thereby calculating the coarse particle ratio.
[0237] The abbreviations used in the present examples represent the following compounds.
[0238] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0239] PMDA: Pyromellitic Dianhydride
[0240] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl
[0241] BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane
[0242] TPE-R: 1,3-bis(4-aminophenoxy)benzene
[0243] BTDA: 3,3',4,4'-Benzophenonetetracarboxylic dianhydride
[0244] DDA: C36 aliphatic diamine [manufactured by Croda Japan Co., Ltd., trade name: PRIAMINE 1074, purified by distillation, amine value: 210 mgKOH / g, mixture of cyclic and chain diamine dimers, component (a): 97.9%, component (b): 0.3%, component (c): 1.8%
[0245] In addition, "%" of component (a), component (b), and component (c) means the area percentage of the chromatogram in GPC measurement. In addition, the molecular weight of DDA is calculated by the following formula.
[0246] Molecular weight = 56.1 × 2 × 1000 / amine value]
[0247] NMP: N-methyl-2-pyrrolidone
[0248] DMAc: N,N-dimethylacetamide
[0249] N-12: Dodecanedioic acid dihydrazide
[0250] OP945: organic phosphinate aluminum salt (manufactured by Clariant Japan, trade name: Exolit OP945, D 50 :2.1μm,D 95 : 3.0μm, maximum particle size: 6.7μm, proportion of particles with a diameter exceeding 10μm: 0% by volume)
[0251] OP935: organic phosphinate aluminum salt (manufactured by Clariant Japan, trade name: Exolit OP935, D 50 :2.7μm,D 95 : 6.8μm, maximum particle size: 11.5μm, proportion of particles with a diameter exceeding 10μm: 1.07% by volume)
[0252] (Synthesis example 1)
[0253] <Preparation of resin solution for adhesive layer>
[0254] Under nitrogen flow, 45.43 parts by weight of BTDA (0.1410 parts by mole), 74.57 parts by weight of DDA (0.1396 parts by mole), 168 parts by weight of NMP and 112 parts by weight of xylene were charged into a reaction tank and mixed thoroughly at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated and stirred for 5 hours, and 98 parts by weight of xylene was added to prepare a polyimide solution 1 (solid content: 30% by weight, weight average molecular weight: 52,800) after imidization.
[0255] (Synthesis example 2)
[0256] <Preparation of polyamic acid solution for insulating resin layer>
[0257] Under nitrogen flow, 78.36 parts by weight of m-TB (0.3691 molar parts) and 7.97 parts by weight of BAPP (0.0194 molar parts) and DMAc with a solid content concentration of 15% by weight after polymerization were added to the reaction tank, stirred and dissolved at room temperature. Next, 50.10 parts by weight of PMDA (0.2297 molar parts) and 45.05 parts by weight of BPDA (0.1531 molar parts) were added, and the polymerization reaction was continued by stirring at room temperature for 3 hours to prepare a polyamic acid solution 1 (viscosity: 28,900 mPa·s). For the polyimide film obtained by applying the polyamic acid solution 1 to a substrate, drying it and imidizing it, the storage elastic coefficient was measured, and the result was "non-thermoplastic".
[0258] (Synthesis example 3)
[0259] <Preparation of polyamic acid solution for insulating resin layer>
[0260] 3.48 parts by weight of m-TB (0.0164 parts by mole), 27.14 parts by weight of TPE-R (0.0928 parts by mole), DMAc in an amount of 12% by weight of solid content after polymerization, 9.72 parts by weight of PMDA (0.0446 parts by mole) and 19.66 parts by weight of BPDA (0.0668 parts by mole) were added as raw material compositions, and polyamic acid solution 2 (viscosity: 2,650 mPa·s) was prepared in the same manner as in Synthesis Example 2. The storage elastic coefficient of the polyimide film obtained by applying the polyamic acid solution 2 on a substrate, drying it and imidizing it was measured, and the result was "thermoplastic".
[0261] <Preparation of resin varnish for adhesive layer>
[0262] (Mixture Example 1)
[0263] 9.47 parts by weight of N-12 were mixed into 100.00 parts by weight of polyimide solution 1, and 131.11 parts by weight of OP945 (48.28 parts by weight relative to 100 parts by weight of the final resin component), 120.33 parts by weight of xylene, and 21.00 parts by weight of NMP were added to dilute, and stirred using a rotation and revolution mixer. Then, 773.67 parts by weight of polyimide solution 1 and 19.33 parts by weight of xylene were added, and stirred for 2 hours to prepare an adhesive composition 1 (viscosity: 2,910 mPa·s).
[0264] (Mixture Example 2)
[0265] 9.47 parts by weight of N-12 were mixed into 100.00 parts by weight of polyimide solution 1, and 157.33 parts by weight of OP945 (57.94 parts by weight relative to 100 parts by weight of the final resin component), 128.67 parts by weight of xylene, and 22.00 parts by weight of NMP were added to dilute, and stirred using a rotary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 16.67 parts by weight of xylene were added, and stirred for 2 hours to prepare an adhesive composition 2 (viscosity: 3,150 mPa·s).
[0266] (Mixture Example 3)
[0267] 9.47 parts by weight of N-12 were mixed into 100.00 parts by weight of polyimide solution 1, and 183.56 parts by weight of OP945 (67.59 parts by weight relative to 100 parts by weight of the final resin component), 137.00 parts by weight of xylene, and 23.00 parts by weight of NMP were added to dilute, and stirred using a rotary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 15.00 parts by weight of xylene were added, and stirred for 2 hours to prepare an adhesive composition 3 (viscosity: 3,320 mPa·s).
[0268] (Mixture Example 4)
[0269] 9.47 parts by weight of N-12 were mixed into 100.00 parts by weight of polyimide solution 1, and 65.56 parts by weight of OP945 (24.14 parts by weight relative to 100 parts by weight of the final resin component), 95.33 parts by weight of xylene, and 18.33 parts by weight of NMP were added to dilute, and stirred using a rotary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 26.67 parts by weight of xylene were added, and stirred for 2 hours to prepare an adhesive composition 4 (viscosity: 2,230 mPa·s).
[0270] (Preparation Example 5)
[0271] 9.47 parts by weight of N-12 were mixed into 100.00 parts by weight of polyimide solution 1, and 91.78 parts by weight of OP945 (33.80 parts by weight relative to 100 parts by weight of the final resin component), 103.67 parts by weight of xylene, and 19.00 parts by weight of NMP were added to dilute, and stirred using a rotary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 24.00 parts by weight of xylene were added, and stirred for 2 hours to prepare an adhesive composition 5 (viscosity: 2,450 mPa·s).
[0272] (Preparation Example 6)
[0273] 9.47 parts by weight of N-12 were mixed into 100.00 parts by weight of polyimide solution 1, and 104.89 parts by weight of OP945 (38.62 parts by weight relative to 100 parts by weight of the final resin component), 112.00 parts by weight of xylene, and 20.00 parts by weight of NMP were added to dilute, and stirred using a rotary mixer. Then, 773.67 parts by weight of polyimide solution 1 and 21.67 parts by weight of xylene were added, and stirred for 2 hours to prepare an adhesive composition 6 (viscosity: 2,690 mPa·s).
[0274] (Mixture Example 7)
[0275] 145.33 parts by weight of xylene and 22.00 parts by weight of NMP were added to 873.67 parts by weight of the polyimide solution 1 for dilution, 9.47 parts by weight of N-12 and 157.33 parts by weight of OP935 (57.94 parts by weight relative to 100 parts by weight of the final resin component) were prepared, and then stirred for 2 hours to prepare an adhesive composition 7 (viscosity: 3,030 mPa·s).
[0276] (Production example 1)
[0277] <Preparation of Single-sided Metal-clad Laminated Plate 1>
[0278] On a long strip of copper foil 1 (electrolytic copper foil, thickness: 12μm, surface roughness Rz on the resin layer side: 0.6μm, width: 0.5m), a polyamic acid solution 2 is evenly applied using a notch wheel coater in a manner that the thickness after curing is about 2μm to 3μm, and then the solution is heated and dried at 145°C to remove the solvent. Next, the polyamic acid solution 1 is evenly applied thereon in a manner that the thickness after curing is about 14μm to 16μm, and the solution is heated and dried at 80°C to 145°C to remove the solvent. Furthermore, the polyamic acid solution 2 is evenly applied thereon in a manner that the thickness after curing is about 2μm to 3μm, and then the solution is heated and dried at 145°C to remove the solvent. Furthermore, a staged heat treatment is performed from 120°C to 360°C to complete imidization, thereby preparing a long strip of single-sided metal-clad laminate 1 with a polyimide layer thickness of 20μm.
[0279] <Preparation of polyimide film 1>
[0280] The copper foil layer of the single-sided metal laminate 1 was etched away using an aqueous solution of ferric chloride to prepare a polyimide film 1 with a thickness of 20 μm. The CTE was 20 ppm / K, the Dk and Df of the humidity-adjusted plate were 3.40 and 0.0033, and the Dk and Df of the water-absorbed plate were 3.40 and 0.0070, respectively. In addition, the Tg was 290°C, and the storage elastic coefficients at 30°C and 125°C were 8.9×10 9 Pa, 5.9×10 9 Pa.
[0281] [Example 1]
[0282] On the insulating resin layer side of the long single-sided metal-clad laminate 1, the adhesive composition 1 prepared in the formulation example 1 was continuously and uniformly applied using a die coater in a manner that the thickness after drying was 60 μm, and then the single-sided metal-clad laminate 1a' with an adhesive layer was obtained by stepwise heating and drying from 80°C to 160°C to remove the solvent. In addition, the adhesive layer was peeled off from the single-sided metal-clad laminate 1a' with an adhesive layer to obtain an adhesive layer sheet 1. The tensile elastic modulus of the adhesive layer sheet 1 was 1.07 GPa, the tensile elongation was 183%, the tensile strength was 24 MPa, the storage elastic modulus at 80°C was 12.1 MPa, the CTE was 111 ppm / K, the Dk and Df during humidity adjustment were 2.70 and 0.0023, respectively, and the thickness variation was 0.77 μm. In addition, in the evaluation of the filler shedding property, there was no void in the cross section of the adhesive layer, and no shedding of OP945 was confirmed. Furthermore, even when observing the surface field of any ten locations, no filler component having a particle diameter exceeding 10 μm and no filler loss portion having a major diameter exceeding 10 μm were confirmed within the surface field of 100 μm×100 μm.
[0283] Next, the adhesive layer side surface of the single-sided metal-clad laminate 1a' with an adhesive layer is placed in contact with the insulating resin layer side surface of the other single-sided metal-clad laminate 1, and while being conveyed via a guide roller, they are continuously overlapped and continuously thermocompressed using a heating and pressing device having at least a pair of metal heating and pressing rollers (roller surface temperature: 80°C) and a roller covered with silicone rubber, thereby obtaining a double-sided copper-clad laminate 1. The double-sided copper-clad laminate 1 has no wrinkles and good adhesion over the entire surface.
[0284] [Example 2]
[0285] The adhesive composition 2 is set as the adhesive composition 2, and the single-sided metal-clad laminate 2a' with an adhesive layer is obtained in the same manner as in Example 1. In addition, the adhesive layer is peeled off from the single-sided metal-clad laminate 2a' with an adhesive layer to obtain an adhesive layer sheet 2. The tensile elastic modulus of the adhesive layer sheet 2 is 1.03 GPa, the tensile elongation is 165%, the tensile strength is 20 MPa, the storage elastic modulus at 80°C is 14.1 MPa, the CTE is 103 ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0025, respectively, and the thickness is uneven by 0.65 μm. In addition, in the evaluation of the filler shedding property, there is no void in the cross section of the adhesive layer, and no shedding of OP945 is confirmed. Furthermore, even if the surface field of any ten parts is observed, no filler component with a particle diameter exceeding 10 μm and a filler shedding portion with a long diameter exceeding 10 μm in the surface field of 100 μm×100 μm are confirmed.
[0286] Next, a double-sided copper-clad laminate 2 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 2a' with an adhesive layer was used. The double-sided copper-clad laminate 2 had no wrinkles and good adhesion over the entire surface.
[0287] [Example 3]
[0288] The adhesive composition 3 is set as the adhesive composition, and the single-sided metal-clad laminate 3a' with an adhesive layer is obtained in the same manner as in Example 1 except that the adhesive layer is peeled off from the single-sided metal-clad laminate 3a' with an adhesive layer to obtain an adhesive layer sheet 3. The tensile elastic modulus of the adhesive layer sheet 3 is 1.09 GPa, the tensile elongation is 176%, the tensile strength is 19 MPa, the storage elastic modulus at 80°C is 17.4 MPa, the CTE is 98 ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0025, respectively, and the thickness is uneven by 0.61 μm. In addition, in the evaluation of the filler shedding property, there is no void in the cross section of the adhesive layer, and no shedding of OP945 is confirmed. Furthermore, even if the surface field of any ten parts is observed, no filler component with a particle diameter exceeding 10 μm and a filler shedding portion with a long diameter exceeding 10 μm in the surface field of 100 μm×100 μm are confirmed.
[0289] Next, a double-sided copper-clad laminate 3 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 3a' with an adhesive layer was used. The double-sided copper-clad laminate 3 had no wrinkles and good adhesion over the entire surface.
[0290] [Example 4]
[0291] The thickness after drying becomes 75 μm, and a single-sided metal-clad laminate 4a' with an adhesive layer is obtained in the same manner as in Example 2 except that the adhesive layer is peeled off from the single-sided metal-clad laminate 4a' with an adhesive layer to obtain an adhesive layer sheet 4. The tensile elastic modulus of the adhesive layer sheet 4 is 1.04 GPa, the tensile elongation is 166%, the tensile strength is 21 MPa, the storage elastic modulus at 80°C is 14.3 MPa, the CTE is 105 ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0025, respectively, and the thickness is uneven by 1.22 μm. In addition, in the evaluation of filler shedding, there are no voids in the cross section of the adhesive layer, and no shedding of OP945 is confirmed. Furthermore, even if the surface field of any ten parts is observed, no filler components with a particle diameter exceeding 10 μm and filler shedding parts with a long diameter exceeding 10 μm are confirmed to exist within the surface field of 100 μm×100 μm.
[0292] Next, a double-sided copper-clad laminate 4 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 4a' with an adhesive layer was used. The double-sided copper-clad laminate 4 had no wrinkles and good adhesion over the entire surface.
[0293] Comparative Example 1
[0294] The adhesive composition 4 was set, and a single-sided metal-clad laminate 5a' with an adhesive layer was obtained in the same manner as in Example 1 except that the adhesive layer was peeled off from the single-sided metal-clad laminate 5a' with an adhesive layer to obtain an adhesive layer sheet 5. The tensile elastic modulus of the adhesive layer sheet 5 was 0.87 GPa, the tensile elongation was 207%, the tensile strength was 31 MPa, the storage elastic modulus at 80°C was 6.1 MPa, the CTE was 122 ppm / K, the Dk and Df during humidity adjustment were 2.70 and 0.0022, respectively, and the thickness was uneven by 1.05 μm. In addition, in the evaluation of filler shedding, there was no void in the cross section of the adhesive layer, and no shedding of OP945 was confirmed. Furthermore, even if the surface field of any ten parts was observed, no filler component with a particle diameter exceeding 10 μm and a filler shedding portion with a long diameter exceeding 10 μm within the surface field of 100 μm×100 μm were confirmed.
[0295] Next, a double-sided copper-clad laminate 5 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 5a' with an adhesive layer was used. Wrinkles were generated in the double-sided copper-clad laminate 5, and poor adhesion due to the wrinkles occurred.
[0296] Comparative Example 2
[0297] The adhesive composition 5 is set as the adhesive composition, and the single-sided metal-clad laminate 6a' with an adhesive layer is obtained in the same manner as in Example 1. In addition, the adhesive layer is peeled off from the single-sided metal-clad laminate 6a' with an adhesive layer to obtain an adhesive layer sheet 6. The tensile elastic modulus of the adhesive layer sheet 6 is 0.93GPa, the tensile elongation is 199%, the tensile strength is 27MPa, the storage elastic modulus at 80°C is 8.4MPa, the CTE is 118ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0022, respectively, and the thickness is uneven by 0.99μm. In addition, in the evaluation of filler shedding, there are no voids in the cross section of the adhesive layer, and no shedding of OP945 is confirmed. Furthermore, even if the surface field of any ten parts is observed, no filler component with a particle diameter exceeding 10μm and a filler shedding portion with a long diameter exceeding 10μm in the surface field of 100μm×100μm are confirmed.
[0298] Next, a double-sided copper-clad laminate 6 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 6a' with an adhesive layer was used. Wrinkles were generated in the double-sided copper-clad laminate 6, and poor adhesion due to the wrinkles occurred.
[0299] Comparative Example 3
[0300] The adhesive composition 6 is set, and a single-sided metal-clad laminate 7a' with an adhesive layer is obtained in the same manner as in Example 1 except that the adhesive layer is peeled off from the single-sided metal-clad laminate 7a' with an adhesive layer to obtain an adhesive layer sheet 7. The tensile elastic modulus of the adhesive layer sheet 7 is 0.97 GPa, the tensile elongation is 192%, the tensile strength is 26 MPa, the storage elastic modulus at 80°C is 9.7 MPa, the CTE is 112 ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0023, respectively, and the thickness is uneven by 0.85 μm. In addition, in the evaluation of filler shedding, there are no voids in the cross section of the adhesive layer, and no shedding of OP945 is confirmed. Furthermore, even if the surface field of any ten parts is observed, no filler components with a particle diameter exceeding 10 μm and filler shedding parts with a long diameter exceeding 10 μm are confirmed to exist within the surface field of 100 μm×100 μm.
[0301] Next, a double-sided copper-clad laminate 7 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 7a' with an adhesive layer was used. The double-sided copper-clad laminate 7 had slight wrinkles, and poor adhesion due to the wrinkles occurred.
[0302] Comparative Example 4
[0303] The adhesive composition 4 is set as the adhesive composition, and the single-sided metal-clad laminate 8a' with an adhesive layer is obtained in the same manner as in Example 4 except that the adhesive layer is peeled off from the single-sided metal-clad laminate 8a' with an adhesive layer to obtain an adhesive layer sheet 8. The tensile elastic modulus of the adhesive layer sheet 8 is 0.91 GPa, the tensile elongation is 205%, the tensile strength is 30 MPa, the storage elastic modulus at 80°C is 5.9 MPa, the CTE is 120 ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0022, respectively, and the thickness is uneven by 1.50 μm. In addition, in the evaluation of the filler shedding property, there is no void in the cross section of the adhesive layer, and no shedding of OP945 is confirmed. Furthermore, even if the surface field of any ten parts is observed, no filler component with a particle diameter exceeding 10 μm and a filler shedding portion with a long diameter exceeding 10 μm in the surface field of 100 μm×100 μm are confirmed.
[0304] Next, a double-sided copper-clad laminate 8 was obtained in the same manner as in Example 1 except that a single-sided metal-clad laminate 8a' with an adhesive layer was used. Wrinkles were generated in the double-sided copper-clad laminate 8, and poor adhesion due to the wrinkles occurred.
[0305] [Example 5]
[0306] The adhesive composition 2 is applied on one side of a long strip of release PET film 1 (manufactured by Dongshan Film Co., Ltd., trade name: HY-S05, thickness: 25 μm) in such a manner that the thickness after drying becomes 60 μm, and the film is dried by heating in stages from 80°C to 160°C, the solvent is removed, and the adhesive layer is peeled off from the release PET film 1, thereby obtaining an adhesive layer sheet 9 with a thickness of 60 μm. The tensile elastic modulus of the adhesive layer sheet 9 is 1.05 GPa, the storage elastic modulus at 80°C is 13.9 MPa, the tensile elongation is 163%, the tensile strength is 20 MPa, the CTE is 100 ppm / K, the Dk and Df during humidity adjustment are 2.70 and 0.0025, respectively, and the thickness variation is 0.67 μm. In addition, in the evaluation of the filler shedding property, as shown in FIG. Figure 5 There are no gaps in the cross section of the adhesive layer, and no OP945 dropout is confirmed. Furthermore, even when observing any ten locations in the surface field, no filler components with a particle size exceeding 10 μm and no filler dropout parts with a major axis exceeding 10 μm are confirmed within the surface field of 100 μm×100 μm.
[0307] The insulating resin layers of two long strips of single-sided metal-clad laminated plates 1 are placed in contact with each other on both sides of the bonding layer 9, and while being conveyed via guide rollers, they are continuously overlapped and continuously heat-pressed using a heating and pressing device having at least a pair of metal heating and pressing rollers (roller surface temperature: 80° C.) and a roller covered with silicone rubber, thereby obtaining a double-sided copper-clad laminated plate 9. The double-sided copper-clad laminated plate 9 has no wrinkles and good adhesion over the entire surface.
[0308] Comparative Example 5
[0309] The adhesive composition 7 was used as an example. Except for this, a single-sided metal-clad laminate 10a' with an adhesive layer was obtained in the same manner as in Example 1. In addition, the adhesive layer was peeled off from the single-sided metal-clad laminate 10a' with an adhesive layer to obtain an adhesive layer sheet 10. The adhesive layer sheet 10 had a tensile elastic modulus of 1.05 GPa, a tensile elongation of 162%, a tensile strength of 19 MPa, a storage elastic modulus of 14.2 MPa at 80°C, a CTE of 102 ppm / K, Dk and Df of 2.70 and 0.0025, respectively, and a thickness variation of 0.68 μm. In addition, in the evaluation of the filler shedding property, as shown in FIG. Figure 6 As shown, filler components with a particle size of 10 μm or more and voids in the cross section of the adhesive layer (filler fall-off portions with a major diameter exceeding 10 μm) were observed, and the state of fall-off of coarse particles in OP935 was observed.
[0310] As shown in the above embodiment, the adhesive layer sheets 1 to 4 and 9 are prepared with high concentration of OP945, and the tensile elastic coefficient and the storage elastic coefficient at 80°C are increased, and it is difficult to produce deformation caused by shear stress when laminating the single-sided metal-clad laminate, and the effect of suppressing the wrinkles caused by the deformation is obtained. In addition, it is believed that by preparing OP945 at a high concentration, it is easy to produce friction between inorganic particles in the adhesive composition, suppressing the fluidity at high temperature, and thus reducing the thickness unevenness. In addition, in Comparative Example 5, by the existing preparation method of directly preparing fillers in the diluted resin varnish, when preparing the adhesive layer sheet by preparing a resin composition with a maximum particle size of 10μm or more of OP935 at a high concentration, the particle size in the adhesive layer sheet is large, and the filler is easy to fall off due to the shear stress caused by cutting. Therefore, in the form of the comparative example, there is the following concern: foreign matter is generated in the process due to the fall of fillers during cutting, or poor through-hole plating is caused by the fall of fillers during drilling and hole opening.
[0311] <Preparation of Laminated Films 1 to 9>
[0312] Double-sided copper-clad laminates 1 to 9 are slit-processed, cut into specified sizes, placed in a constant temperature bath, and heat-treated at 180° C. for 24 hours. The copper foil layer is then etched away using an aqueous solution of ferric chloride to prepare laminate films 1 to 9 having a thickness of 100 μm to 125 μm.
[0313] Table 1 shows the dielectric properties of the adhesive layer sheets 1 to 9 and the dielectric properties and flame retardancy evaluation results of the laminated films 1 to 9.
[0314] [Table 1]
[0315]
[0316] The Df of the bonding layer during humidity control tends to increase as OP945 increases, but the Df of laminated films 1 to 9 show the same value. In addition, the Df of the bonding layer during water absorption shows a tendency to increase more significantly as OP945 increases than during humidity control. On the other hand, in Examples 1 to 5, the Df of the laminated film during water absorption shows a value lower than the Df estimated value calculated based on the Df of the polyimide film 1 and the bonding layer during water absorption in consideration of the thickness ratio. It is believed that even if the Df of the bonding layer during water absorption deteriorates, the water absorption of the bonding layer is suppressed by adopting a structure in which the polyimide film 1 is laminated on both sides.
[0317] The estimated Df value of the laminated film at the time of water absorption was calculated based on the following formula (1).
[0318] [Number 1]
[0319]
[0320] Df T : Estimated Df value of laminated film when absorbing water
[0321] T T : The thickness of the laminated film
[0322] Df P : Df of polyimide film 1 when absorbing water
[0323] T P : Total thickness of polyimide film 1 (two layers)
[0324] Df A : Df of the water absorption of the bonding layer
[0325] T A :Thickness of the next layer
[0326] Regarding flame retardancy, the probability that the burning time (t1) of 10 samples is less than 10 seconds is more than 80% in the laminated films 1 to 4 and 9 shown in the embodiments and is evaluated as ○, while it is less than 80% in the laminated films 5 to 8 shown in the comparative examples and is evaluated as ×.
[0327] As described above in detail, the laminate and the metal-clad laminate according to the embodiment of the present invention have excellent dielectric properties, flame retardancy, and processability, and are considered to be designed to suppress uneven thickness and wrinkles during lamination.
[0328] As mentioned above, although embodiment of this invention was described in detail for the purpose of illustration, this invention is not limited to the said embodiment, Various deformation|transformation is possible.
Claims
1. A laminate comprising: a first insulating resin layer; a second insulating resin layer; as well as The bonding layer is laminated between the first insulating resin layer and the second insulating resin layer in a manner abutting against these layers, and the laminate is characterized in that: The total thickness T1 of the first insulating resin layer, the adhesive layer and the second insulating resin layer is within a range of 70 μm to 500 μm, the thickness T2 of the adhesive layer is within a range of more than 50 μm and less than 450 μm, and the ratio (T2 / T1) of T2 to T1 is within a range of more than 0.5 and less than 0.96, The adhesive layer comprises a resin component and a filler component, The resin component contains a polyimide, the polyimide having a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition relative to all diamine residues, wherein the dimer diamine composition mainly contains a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl or amino groups, The filler component includes a metal salt of an organic phosphinic acid, and a weight ratio of the filler component relative to 100 parts by weight of the total amount of the resin component is within a range of more than 40 parts by weight and not more than 90 parts by weight.
2. A laminate according to claim 1, wherein within a surface field of view of 100 μm × 100 μm when a thickness direction cross section of the bonding layer is observed under a scanning electron microscope, the total area ratio of filler components with a particle diameter exceeding 10 μm and filler detachment portions with a long diameter exceeding 10 μm is less than 1% as the average value of the surface field of view at any ten locations. 3 . The laminate according to claim 1 , wherein the polyimide is a polyimide having a ketone group in a molecule, and the resin component contains a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the ketone group. 4 . The laminate according to claim 1 , wherein the polyimide forms a crosslinked structure by a reaction between a molecule having a keto group and a crosslinking agent having a functional group that undergoes a nucleophilic reaction with the keto group. The laminate according to claim 1 , wherein the tensile elastic coefficient of the adhesive layer is within a range of 1.0 GPa to 1.2 GPa. 6 . The laminate according to claim 1 , wherein the adhesive layer has a storage elastic coefficient at 80° C. in a range of 10 MPa to 20 MPa.
7. The laminate according to claim 1, wherein: The first insulating resin layer and the second insulating resin layer are multi-layered polyimide layers including a non-thermoplastic polyimide layer and a thermoplastic polyimide layer.
8. The laminate according to claim 7, characterized in that The outermost layer of the multi-layer polyimide layer is a thermoplastic polyimide layer.
9. The laminate according to claim 1, characterized in that The length in the width direction (lateral direction) is in the range of 0.2 m to 2.0 m, and is in an elongated shape. 10 . A metal-clad laminate comprising: the laminate according to claim 1 ; and a metal layer laminated on one surface or both surfaces of the laminate. 11 . A circuit board comprising: the laminate according to claim 1 ; and a wiring layer laminated on one surface or both surfaces of the laminate.
12. An electronic component, characterized in that: Comprising the circuit substrate as claimed in claim 11.
13. An electronic device, characterized in that: Comprising the circuit substrate as claimed in claim 11.
14. An adhesive resin composition comprising a resin component, a filler component and an organic solvent, wherein: The resin component contains a polyimide, the polyimide having a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition relative to all diamine residues, wherein the dimer diamine composition mainly contains a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl or amino groups, The filler component contains a metal salt of an organic phosphinic acid, The weight ratio of the filler component relative to 100 parts by weight of the total amount of the resin component is in the range of more than 40 parts by weight and not more than 90 parts by weight, When the film is formed with a thickness in the range of more than 50 μm and 450 μm or less, the tensile elastic coefficient is in the range of 1.0 GPa or more and 1.2 GPa or less, and the storage elastic coefficient at 80° C. is in the range of 10 MPa or more and 20 MPa or less.
15. A method for producing an adhesive resin composition, comprising the following steps (i) and (ii); (i) a step of obtaining a filler dispersion by mixing a part of the resin component and the filler component in an organic solvent and stirring the mixture; and (ii) a step of obtaining the adhesive resin composition by mixing the remaining portion of the resin component together with an organic solvent into the filler dispersion and stirring the mixture, In the step (i), the weight ratio of the resin component in the filler dispersion is set within the range of 3 parts by weight to 15 parts by weight relative to 100 parts by weight of the final total amount of the resin component, and the solid content concentration in the filler dispersion is adjusted to be within the range of 40% by weight to 60% by weight. In the step (ii), the weight ratio of the filler component in the adhesive resin composition is within the range of more than 40 parts by weight and not more than 90 parts by weight relative to 100 parts by weight of the final total amount of the resin component.
16. An adhesive film comprising a resin component and a filler component, wherein: The resin component contains a polyimide, the polyimide having a tetracarboxylic acid residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and containing 40 mol % or more of diamine residues derived from a dimer diamine composition relative to all diamine residues, wherein the dimer diamine composition mainly contains a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl or amino groups, The filler component contains a metal salt of an organic phosphinic acid, The weight ratio of the filler component relative to 100 parts by weight of the total amount of the resin component is in the range of more than 40 parts by weight and not more than 90 parts by weight, The thickness is within the range of more than 50 μm and less than 450 μm. The tensile elastic coefficient is in the range of 1.0 GPa or more and 1.2 GPa or less, and the storage elastic coefficient at 80° C. is in the range of 10 MPa or more and 20 MPa or less.